Precise H2 supply enables quantitative control of on-demand deep nitrate removal while preserving denitrification completeness - Ge Yan; Zhen-Xiang Jiang; Jia-Le Wu; Ting Wang; Jun-Tong Hu; Li-Wen Qiu; Chen Zhou; Hongqiang Ren (Water Research, 2026)

Rapid phase separation assisted hydrogel evaporator for solar desalination and water environmental purification - Jianbo Zhang; Jinming Yu; Tongyu Zhang; Zhenjie Ma; Yutian Wang; Bo Ge; Hui Zhao; Tonghui Zhang; Guina Ren; Zhaozhu Zhang (Desalination, 2026)

Bipyridine-based covalent organic framework for trace-level nanofluidic detection of chlorobenzoquinone - Xu-Qin Ran; Xin-Ge Cai; Xiao-Jiao Ren; Xiu-Ping Yan; Hai-Long Qian (Chemical Engineering Journal, 2026)

Disruption of progesterone synthesis by PBDEs: Potent inhibition of human and rat placental 3β-hydroxysteroid dehydrogenase by the metabolite 4-Bromodiphenyl ether - Lubin Xie; Qianjin Fei; Ming Su; Yunbing Tang; Yang Zhu; Ren-shan Ge; Ping Duan; Chengshuang Pan (Toxicology and Applied Pharmacology, 2026)

Structure-activity relationship of per- and Polyfluoroalkyl substances as inhibitors of human and rat 17β-Hydroxysteroid dehydrogenase 3 - Chengshuang Pan; Jingjing Li; Fuhong Tian; Chentao Ding; Shaowei Wang; Ren-shan Ge; Qianjin Fei; Yang Zhu (Toxicology and Applied Pharmacology, 2026)

Phosphatidic acid mediates the crosstalk between ethylene and lipid metabolism to confer chilling tolerance - Ke Wang; Bei Zhou; Ge Zhu; Yue Sun; Xue-ren Yin; Qing-feng Niu (Postharvest Biology and Technology, 2026)

Interfacial polymerization for sustainable microencapsulation: Bio-based core/shell design, mechanistic principles, and emerging applications - Limin Gu; Xueqing Qin; Ziyan Ren; Yan Su; Shuai Li; Linya Zhang; Yanrui Ge; Fengxia Sun (Journal of Environmental Chemical Engineering, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Climate and soil properties drive microplastic enrichment patterns in agricultural soils across a multi-country survey - Martine Graf; Michaela K. Reay; Yingming Sun; Fan Ding; Siyang Ren; Kai Wang; Changrong Yan; Shitong Li; Tida Ge; Xuejun Liu; Ruimin Qi; Jixiao Cui; et al. (Environmental Pollution, 2026)

Cu2Se-Cu2O heterointerface layer enables robust zinc deposition at high current via synergistic selective adsorption and kinetics-enhanced ion transport - Lu Wang; Yamei Liu; Xiaofan Tian; Lijin Xie; Zhenchao Li; Yuxin Ge; Hongwei He; Haichao Chen; KuiKui Wang; Daming Zhu; Xiaochuan Ren (Chemical Engineering Journal, 2026)

3D solid-liquid heterogeneous anode/electrolyte interlayer for Zn anode: The trade-off between spatial regulation and ion transport kinetics - Haifeng Bian; Yilun Ren; Shunshun Jia; Qing Zhou; Ge Xue; Qimeng Wang; Haoran Wang; Jian Gu; Yujie Ma; Xiangkang Meng (Chemical Engineering Journal, 2026)

Proteomics-guided multivalent capture and integrated amplification enable profiling of tumor-derived extracellular vesicles in gastric cancer - Ke Ge; Yongan Ren; Pengcheng Wang; Guangzhong Ma; Bo Yao; Changku Jia; Yuanyu Wang; Kai Ye (Chemical Engineering Journal, 2026)

Hidden hormesis of perfluorobutanesulfonate on anaerobic co-digestion: Impacts on metabolic activity and microbial community structure - Jialin Liang; Zibo Zhan; Jingsai Ren; Xidan Feng; Dongdong Ge; Liwen Luo (Chemical Engineering Journal, 2026)

Chain-length-selective inhibition of human and rat steroid 5α-reductase type 1 by alkyltrimethylammonium chloride disinfectants: kinetic, surface plasmon resonance, computational, and network toxicology analyses with implications for neurosteroidogenesis - Junying Chen; Jiaqi Chen; Ying Chen; Jinmei Xia; Haonan Fang; Putian Zhang; Ren-shan Ge; Yiyan Wang (Chemico-Biological Interactions, 2026)

Hydrological controls dominate greenhouse gas emissions in aquatic–terrestrial ecotones under extreme weather - Jingyun Yin; Wenbin Bian; Ke Xu; Liyu Pan; Di He; Chenyu Wang; Xiaohua Song; Xiaotong Ge; Chenyuan Kong; Yuhu Zheng; Hongqiang Ren; Mengmeng Wang; et al. (Journal of Environmental Sciences, 2026)

Salicylate esters inhibit human and rat 11β-Hydroxysteroid dehydrogenase type 2: Mechanistic insights from enzyme kinetics, SPR, and molecular modeling - Yinwei Dai; Zhuoqi Chen; Xiya Ren; Shaowei Wang; Yuli Yang; Yunbing Tang; Renshan Ge (Toxicology and Applied Pharmacology, 2026)

An efficient three-dimensional ocean wave reconstruction method based on adaptive strip-wise stereo matching - Hongfei Yao; Haojie Ren; Hao Ren; Lianxiang Chen; Yue Pan; Jinbo Chen; Hongbo Zhu; Haiyang Ge; Mingqiang Xu (Ocean Engineering, 2026)

Pyrite geochemistry and sulfur isotopes track fluid evolution and Mo enrichment in the giant Jinduicheng porphyry deposit, central China - Xiaoyu Ge; Fan Yang; Martiya Sadeghi; Cun Zhang; Feifan Xu; Weidong Ren (Lithos, 2026)

Neurotoxicological Concerns: Azole Fungicides as Mixed/Noncompetitive Inhibitors of Human and Rat 5α-Reductase 1 - Jiachen Lin; Yinghao Huang; Yilin Xu; Zhiqiang Yu; Chentao Ding; Mengru Li; Yingfen Ying; Ren-shan Ge; Yiluan Wang (Journal of Hazardous Materials, 2026)

Prenatal exposure to polystyrene nanoplastics caused testicular development toxicities and relative mechanisms in male offspring mice from embryo to adulthood - Moxuan Zhao; Junhong Xie; Jingjing Wang; Yue Zhang; Jinglong Xue; Ruxuan Zhang; Ruiyang Zhang; Wei Ge; Lihua Ren; Hongou Wang; Xianqing Zhou (Journal of Environmental Sciences, 2026)

Chlorinated bis-phenolic disinfectants inhibit human and rat aromatase - Wumin Jin; Chaochao Gong; Yilin Xu; Lubin Xie; Xishi Chen; Haonan Fang; Ren-shan Ge (Chemico-Biological Interactions, 2026)

Identification and Heterologous Spatial Distribution of Eleven Novel Brominated Flame Retardants in Soil from Three Petrochemical Industrial Parks and a Flame Retardant Manufacturing Base - Helong Ren; Meibao Li; Chaoyang Long; Xiang Ge; Zhaofa Huang; Yingxin Yu (Water, Air, & Soil Pollution, 2026)

A Wind Data Quality Control Algorithm Utilizing Deep Learning-Based Association Test Rules - Ruidi Ma; Song Gao; Fan Jiang; Bo Yu; Haoqiang Tian; Yanchen Song; Yong Ge; Dianjun Ren; Chenxu Wang (Journal of Marine Science and Engineering, 2026)
Harnessing the powerful learning and modeling capabilities of artificial intelligence, this study introduces a deep learning-driven wind data quality control algorithm that employs correlation verification rules. By constructing a Dual-Track Information Fusion Network (DTF-Net), it captures local temporal variations in wind speed via the temporal track and uncovers physical coupling relationships among temperature, pressure, wind direction, and other variables through the global track. Integrating dynamic three-standard-deviation spike detection with 3δ-RMSE spatial validation based on deep learning predictions, the algorithm enables multi-dimensional collaborative anomaly detection in the absence of neighboring stations. Experimental findings demonstrate that the proposed method achieves Mean Absolute Errors (MAE) of 0.217, 0.398, and 0.462 for 1 h, 12 h, and 24 h wind speed forecasts, respectively, representing a 3.8–61.3% reduction compared to general-purpose models like AutoFormer, ITransformer, and FiLM. The anomaly detection rate for quality control ranges from 0.33% to 9.20%, effectively identifying data aberrations during buoy maintenance, equipment failures, and abrupt changes in short-term weather patterns. This study leverages the powerful learning and modeling capabilities of artificial intelligence to establish a novel and easily understandable intelligent quality-control paradigm for sparse ocean observation networks, providing direct practical value for improving the quality of marine meteorological data assimilation.

Carbon-chain length dictates per- and polyfluorinated substance potency as inhibitors of human and rat 11β-hydroxysteroid dehydrogenase 1 - Congcong Zhao; Zhiqiang Yu; Mengyun Wang; Yingfen Ying; Yunbing Tang; Huitao Li; Ren-shan Ge; Junbo Liang (Toxicology and Applied Pharmacology, 2026)

Nitrogen fertilization drives bacterial turnover versus fungal persistence for straw-derived C and N stabilization in a wheat-maize rotation - Guocui Ren; Xiuli Xin; Haowei Ni; Xianfeng Zhang; Lan Mu; Wenliang Yang; Shuchun Ge; Shaopu Pang; Anning Zhu (Soil and Tillage Research, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

Preliminary insights into the release behavior of dissolved organic matter from aged microplastics in seawater: Effects of aging types - Xi Li; Qimeng Yang; Huimin Ma; Ruru Ge; Xinwei Zhou; Peng Ren (Marine Environmental Research, 2026)

W-Doped Bi2O3 Photocatalyst Based on Bi-MOF: Enhanced Visible-Light-Driven Methylene Blue Degradation and Hydrogen Production via Electronic Structure Modulation - Keren Shi; Xiaoyu Li; Qiaowei Xiao; Ziyan Wang; Wende Yi; Shaoying Ge; Zhenrui Shi; Jianlin Ren; Fuke Wang; Zhiqiang Tian; Huiqin Yao (Journal of Environmental Chemical Engineering, 2026)

Agricultural anthropogenic attribution of nitrate in karst river basin: Insights from nitrate dual isotopes and Bayesian mixing model - Xinyi He; Jie Zeng; Qixin Wu; Qian Zhang; Zhong-Jun Wang; Jie Ren; Qing Ma; Jie Zhang; Xin Ge (Journal of Environmental Management, 2026)

Molecular Evidence for Distinct Coastal Dissolved Organic Matter Responses to Nitrogen and Phosphorus Enrichment - Xin Guo; Junfeng Chen; Xiao Chen; Lianbao Zhang; Gang Li; Hongwei Ren; Bokun Chen; Yubin Hu; Ge Xu; Dingxi Zhang; Chen He; Quan Shi; et al. (Journal of Environmental Sciences, 2026)

The dual role of H2 in a hydrogen-rich atmosphere: mechanisms of coke dissolution loss inhibition and strength enhancement - Jialong Yao; An Li; Rong Ge; Jingchong Yan; Zhanku Li; Weidong Zhang; Zhicai Wang; Zhiping Lei; Shibiao Ren; Hengfu Shui (Fuel, 2026)

Enhancement of ursolic acid (UA), an active ingredient in hawthorn, on the uptake and metabolism of 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside (THSG) derived from Polygonum multiflorum - Runlu Li; Simin Ren; Yunhong Zhao; Ni An; Jingwu Song; Feng Guan; Jian Ge (Food Research International, 2026)

Two-step pyrolysis enabled by bentonite catalysis for the co-production of bioactive humic acid and functional carbon-clay composites - Huanhuan Li; Jiarun Duan; Lijuan Zhang; Yong Wen; Yun Xiang; Chen Qiu; Junmei An; Zhiguo Guo; Yidong Cai; Changchun Ge; Xiaona Ren; Xinjiang Zhou; et al. (Environmental Research, 2026)

Differences between human and rat 5α-Reductase 1 inhibition by phenolic disinfectants: Comparative kinetics and binding modes for neurosteroid synthesis - Xinyu Han; Wanyu Li; Yinghao Huang; Lisha Wang; Tianchi Zhao; Xishi Chen; Hao Lin; Yiyan Wang; Ren-shan Ge; Jianfeng Ma (Chemico-Biological Interactions, 2026)

Elucidating functional group governance for catalytic synthesis of bio-based aromatic amines - Ge-liang Xie; Yu Luo; Kai-cheng Xia; Sheng-ren Li; Lujiang Xu; Zhen Fang (Biomass and Bioenergy, 2026)

Structural determinants of paraben-mediated 11β-hydroxysteroid dehydrogenase 1 inhibition: Integrated mechanistic, kinetic and in silico approaches to cortisol metabolism - Lina Li; Haotian Chen; Yang Zhu; Ren-shan Ge; Chao Chen; Shangqin Chen (Toxicology and Applied Pharmacology, 2026)

Research on high-efficiency region and condition of pectoral fin - Chaowu Sheng; Liwen Nan; Qiaoling Gao; Jiawang Chen; Ziqiang Ren; Han Ge; Haocai Huang (Ocean Engineering, 2026)

Blue light stimulates the release of humic-like substances in a marine diatom Thalassiosira pseudonana - Bokun Chen; Jihua Liu; Ge Xu; Xiao Chen; Wei Zhao; Xue Yang; Hongwei Ren; Gang Li (Marine Environmental Research, 2026)

The effects of the “ten-year fishing ban” on phytoplankton in eutrophic shallow lakes: A case study in Lake Gehu, China - You Ge; Dongpo Xu; Shulun Jiang; Long Ren; Yuxin Ye; Zhiyu Feng; Xue Xue (Journal of Environmental Management, 2026)

Hydrophobicity-driven inhibition of human and rat 11β-hydroxysteroid dehydrogenase 2 by isothiazolinone biocides: Insights from enzyme kinetics and SPR interactions - Nianci Chen; Chuhang Chi; Chunnan Hu; Shaowei Wang; Xiya Ren; Yunbing Tang; Renshan Ge; Qiqi Zhu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Trace phosphate capture and recovery via CNTs@ZIF-8/polysulfone adsorptive membranes - Mengni Ge; Yidan Xu; Jingyi Ren; Jianfeng Zhang; Aihua Zhang; Xiaoying Wu (Chemical Engineering Journal, 2026)

Numerical investigation on the fast pyrolysis of large biomass particles in bubbling beds using the coupled particle-scale and coarse-grained CFD-DEM - Guanlong Ren; Ji Xu; Jiayu Xu; Ying Jia; Wei Ge; Henrik Ström; Jinze Dai; Qingang Xiong (Chemical Engineering Journal, 2026)

Lipophilicity and alkyl chain length govern pyridine quaternary ammonium disinfectants as gonadal 3β-hydroxysteroid dehydrogenase inhibitors: Implications for endocrine disruption - Lingfei Wang; Chaochao Gong; Xiya Ren; Hao Lin; Ren-shan Ge; Congde Chen (Chemico-Biological Interactions, 2026)

Study on the Evolution of Ground Pressure During Collaborative Extraction and the Application of the Superimposed Kelvin Model in Solid Potash Mine - Luwei Zhang; Yongxiang Ge; Gaofeng Ren; Congrui Zhang; Xingyu Tan; Chen Xu; Pulin Kang (Rock Mechanics and Rock Engineering, 2026)

Facile construction of ZnWO4/Ti3C2 MXene type-II heterojunctions via hydrothermal self-assembly: Toward efficient clean energy conversion and environmental remediation - Keren Shi; Xiaoyu Li; Qiaowei Xiao; Ziyan Wang; Wende Yi; Jianlin Ren; Shaoying Ge; Changyi Yang; Huiqin Yao (Fuel, 2026)

Multi-measure ecological restoration drives phytoplankton succession and shifts community assembly in an urban eutrophic lake - Xiaowen Lin; Xiaodong Wu; Xuguang Ge; Fan Xun; Weixiang Ren; Mengdie Zhou; Chenxin Zhong; Chunyan Xiao; Linlin Lei (Ecological Engineering, 2026)

Turning membrane fouling from inevitable to fully reversible via an electric-field repulsion-shield strategy - Yao Du; Jingyi Ren; Jinyi Wang; Jianfeng Zhang; Ziming Zheng; Haimeng Huang; Xue Yan; Lingzhi Cao; Tianmeng Zhang; Jefferson Zhe Liu; Mengni Ge; Xing Yang (Desalination, 2026)

From selection to design: Reshaping aptamer discovery with artificial intelligence - Xin Yang; Shijian Ding; Meishen Ren; Huarui Zhang; Xiaohui Tao; Ning Zhang; Yihao Zhang; Hewen Jiange; Yufei Pan; Shanshan Yao; Luyao Wang; Yuan Ma; et al. (Chemical Engineering Journal, 2026)

Multifunctional sericin/alginate hydrogel integrated with cerium oxide nanozyme for accelerating methicillin-resistant Staphylococcus aureus-infected wound healing - Haiyang Liu; Yingjie Shen; Xin Xie; Xudong Mao; Jin Ren; Cunming Peng; Liangliang Wang; Junbo Zhou; Le Zhang; Lulu Zhang; Changchun Peng; Haixia Ge; et al. (Chemical Engineering Journal, 2026)

Carbon-doping-induced adsorption energy gradient for highly selective alkynol semi‑hydrogenation over PdCu catalysts - Yuan Ren; Jiapeng Huang; Yaohui Zhao; Ruiyun Guo; Yanan Li; Zixin Ge; Qian Wang; Junhao Lu; Anyu Feng; Chenyao Xiao; Mingshang Jin (Chemical Engineering Journal, 2026)

PINK1-PARKIN-dependent mitophagy links diphenyltin exposure to steroidogenic collapse in Rat Leydig Cells during puberty - Qiqi Zhu; Jianqin Yu; Nianci Chen; Lili Tian; Chunnan Hu; Quanxu Chen; Yang Zhu; Ren-Shan Ge; Yi Liu; Xingwang Li (Chemico-Biological Interactions, 2026)

Hydrophobicity, 3D complexity, and steric feature affect salicylate inhibition of human and rat gonadal 3β-hydroxysteroid dehydrogenases: Insights from experiments to 3D-QSAR and in silico docking analysis - Xiya Ren; Zhuoqi Chen; Chengshuang Pan; Yingfen Ying; Yang Zhu; Ren-shan Ge; Yi Liu (Chemico-Biological Interactions, 2026)

Effects of MMP8 inhibitors on chronic unpredictable mild stress-induced neuroinflammation and depressive-like behavior：exploring the underlying molecular mechanisms - Yan Ren; Weikang Chen; Jinhui Wang; Shasha Wu; Ting Linghu; Jinyin Ge; Ruiping Zhang (Psychopharmacology, 2026)

Diverse Neuronal Activity in Barrel Cortex During Self-Grooming and Whisking in Mice - Junye Ge; Baijun Chen; Jinwei Xu; Pengfei Ren; Jialong Li; Tangna Sun; Shengxi Wu; Ying Zang; Wenting Wang (Neuroscience Bulletin, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

PG-DyMamba: a physics-guided dynamic graph Mamba network for significant wave height prediction - Fan Jiang; Yinzhu Zang; Ruidi Ma; Bo Yu; Hui Li; Song Gao; Yong Ge; Dianjun Ren (Frontiers in Marine Science, 2026)
Accurate prediction of Significant Wave Height (SWH) is vital for marine engineering safety, yet balancing computational efficiency with physical consistency in long-sequence modeling remains a challenge for data-driven approaches. To address this, we propose the Physics-Guided Dynamic Graph Mamba Network (PG-DyMamba). By integrating oceanographic priors such as windwave relations, our Physics-Aware Graph Learner adaptively captures time-varying multivariate dependencies. Concurrently, the Mamba architecture processes long historical sequences with linear complexity. To ensure physical plausibility, the model employs a composite loss function based on energy conservation and fluid smoothness, effectively constraining predictions to adhere to fundamental physical laws. Empirical evaluations on Australia, NDBC, and North Sea datasets confirm that PG-DyMamba outperforms state-of-the-art baselines. Notably, the model achieves a 19.2% MSE reduction in 48-step prediction horizon on the Australia dataset, demonstrating its robustness for operational marine applications.

Adsorption mechanisms and weathered surface effects in the neutral flotation separation of feldspar from quartz using a mixed anionic/cationic system - Yuhao He; Yuhan Song; Xiaohui Li; Ge Zhu; Lu Xiang; Zijie Ren (Minerals Engineering, 2026)

Functional validation and mechanistic insights into cadmium removal by the green microalgae Coelastrella tenuitheca S93-3 - Xiumei Luo; Sawera Akram; Ying Wang; Ge Guan; Kangxi Qin; Francois Serneels; Maxime Bonnave; Aijan Tolobekova; Kerimaliev Janybek; Maozhi Ren (Journal of Hazardous Materials, 2026)

Microplastics and bisphenol A co-exposure causes oxidative damage and induces ion regulation disorders in the gills of Portunus trituberculatus - Xiaotian Wang; Zhengjia Wei; Xunjie Huo; Xuerui Ge; Jiayuan Ren; Xiaocong Chen; Tao Zhang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Lupiwighteone exerts anti-aging effects by suppressing NF-κB and activating the MAPKs/Nrf2 signaling pathway - Kun Hu; Ge Ge; Bingjian Wu; Jia Yang; Jie Ren; Lirong Zhang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

In-situ electrochemical conversion-derived porous S/CuWO4 composite cathode with dual catalytic-adsorption functions for aqueous batteries - Xiaofan Tian; Xinliang Huang; Yamei Liu; Lu Wang; Lijin Xie; Yuxin Ge; Zhenchao Li; Mingliang Zhao; Kuikui Wang; Haichao Chen; Zhao Li; Daming Zhu; et al. (Chemical Engineering Journal, 2026)

ABC transporter BrABCG12 mutation results in tender green glossy leaves in Chinese cabbage - Zhichao Gong; Gengxing Song; Chengchuang Huang; Xiaoli Tang; Yanru Ge; Jie Ren; Hui Feng (Theoretical and Applied Genetics, 2026)

Genetic deletion of miR-200a/200b increases growth and feed conversion efficiency in yellow catfish - Xu Wang; Yan Xie; Qiaohong Lin; Yang Xiong; Ying Liu; Si Ge; Qiuen Tan; Zhipeng He; Youbo Jiang; Qingqing Han; Shuang Jin; Peipei Huang; et al. (Science China Life Sciences, 2026)

Correction to: Methyl jasmonate enhances carotenoid accumulation and lignin deposition in carrot taproot - Guang-Long Wang; Jia-Qi Wu; Yan-Xin Ge; Lin-Yan Jia; Cheng-Ling Zhou; Xu-Qin Ren; Ai-Sheng Xiong (Protoplasma, 2026)

Methyl jasmonate enhances carotenoid accumulation and lignin deposition in carrot taproot - Guang-Long Wang; Jia-Qi Wu; Yan-Xin Ge; Lin-Yan Jia; Cheng-Ling Zhou; Xu-Qin Ren; Ai-Sheng Xiong (Protoplasma, 2026)

Processed phellodendri Chinensis cortex attenuates diabetic nephropathy via ferroptosis inhibition through GPX4/SLC7A11/Nrf2/HO-1 signaling pathway - Yue Zhou; Gui Xu; Wenjing Ren; Yang Chen; Shiru Jiang; Shuo Zhang; Xiutong Ge; Hui Gao; Fan Zhang (Journal of Natural Medicines, 2026)

Isoliquiritigenin combined with gemcitabine inhibited lung cancer by suppressing JAK2/STAT3 signaling via lncRNA-p21/miRNA-4534 axis - Chenyue Xu; Cancan Gong; Cheng Wang; Meiping Xie; Mianhua Wu; Dengfeng Ge; Hao Ren; Bin Zhang; Zequn Jiang; Wenting Li (Journal of Natural Medicines, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Global trends in coastal aquaculture ponds: navigating seafood demand and ecological conservation - Dehua Mao; Duanrui Wang; Ming Wang; Hong Yang; Julian R. Thompson; Xiangming Xiao; Yujia Zhang; Kaishan Song; Chunying Ren; Juhua Luo; Ling Luo; Ge Liu; et al. (Science Bulletin, 2026)

Prediction of sea level anomaly from satellite data based on the AVMD-LSTM hybrid model - Fangjie Yu; Zetao Hu; Mengke Ren; Ruotong Li; Junwu Tang; Xinglong Zhang; Ge Chen (Ocean Modelling, 2026)

Trihexyl phosphate exposure disrupts mitophagy and activates mtDNA-cGAS-STING signaling to drive pyroptosis and steroidogenic impairment in Leydig cells - Yinwei Dai; Zhuoqi Chen; Weijian Zhu; Shaowei Wang; Xiya Ren; Yuli Yang; Ren-shan Ge (Journal of Hazardous Materials, 2026)

One-step synthesis of Fe-Mg oxides/hydrochar composites enhanced peroxymonosulfate activation to accelerate organics degradation in aquatic and soil systems - Chao Ren; Mengting Ge; Yanfang Feng; Yueqin Cheng; Huifang Xie; Bingyu Wang (Journal of Environmental Sciences, 2026)

Mechanical behavior and damage mechanism of prefabricated jointed gypsum under uniaxial dynamic impact loading - Yongxiang Ge; Gaofeng Ren; Xinping Li; Chao Zhang; Luwei Zhang; Chen Xu; Congrui Zhang (Bulletin of Engineering Geology and the Environment, 2026)

Refined functional model of precise orbit determination to capture the dynamics of receiver-dependent biases of low earth orbit satellite - Tianhao Wu; Bofeng Li; Haibo Ge; Weikai Miao; Lei Zhang; Wenhao Wu; Weijie Ran; Weijia Ren (GPS Solutions, 2026)

MSI2 expression in single vs. double dominant follicles and its role in Mongolian sheep fecundity - Hao Qinqin; Li Penghui; Zhou Xin; He Yang; Liu Haodong; Li Xiaolong; Yu Mingyang; Zhang Zelin; Fan Jiaxin; Yang Wenchao; Yin Junzhe; Cao Guifang; et al. (Animal Reproduction Science, 2026)

Novel diffusion gradient in thin-films based on antibiofouling Ag/polydopamine membranes for measurement of antibiotics in natural waters - Jiaxing Xie; Fan Ge; Xinyi Yan; Suyu Ren; Yan Wang; Feng Tan (Analytica Chimica Acta, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Synergistic Dust Suppression in Fully Mechanized Mining Faces: Integrating Negative Pressure Induction with Supersonic Atomization - Zhuo Jiang; Deji Jing; Heng Ma; Shaocheng Ge; Shuaishuai Ren (Process Safety and Environmental Protection, 2026)

Thermal evolution characteristics of dibenzothiophene, dibenzofuran and fluorene and their homologues and their geochemical implications - Xueyou Tan; Sijia Nie; Xijun Wang; Wei Peng; Xu Wang; Suyang Cai; Jingwen Zheng; Xiaoyong Wang; Zhushi Ge; Liangliang Ren; Jiang Wei (Organic Geochemistry, 2026)

Dual-facet modulation involving surface carboxyl functionalization and interlayer regulation by CQDs in g-C3N4 for enhanced xylose photooxidation - Shilian Yang; Juan Liu; Chao Huang; Ge Yuan; Bo Lu; Tingzhen Li; Emmanuel Iwuoha; Reverant Crispin; Kasim Ocakoglu; Ren Zou; Linxin Zhong; Xinwen Peng (Chemical Engineering Journal, 2026)

Environmental pyridinium disinfectants impair cortisol metabolism via 11β-hydroxysteroid dehydrogenase 2 inhibition: A cross-species risk evaluation - Chaochao Gong; Xiuzhi Zhang; Yu Zhang; Xishi Chen; Hao Lin; Ren-shan Ge; Youming Zhao (Chemico-Biological Interactions, 2026)

A multi-strategy multi-population cooperative optimization algorithm for drinking water pollution source identification - Han Wang; Qinghua Wu; Yang Ge; Zhijun Ren; Xuesong Yan (Swarm and Evolutionary Computation, 2026)

Particulate matter emissions from GDI gasoline engines: Systematic analysis of operating conditions and fuel injection - Yanxu Ren; Lijun Hao; Yunshan Ge; Xin Wang; Jianwei Tan (Fuel, 2026)

Microplastics and bisphenol A exposure induce hepatopancreatic damage and lipid metabolism disorders in Portunus trituberculatus - Tao Zhang; Biqing Wen; Xunjie Huo; Jiayuan Ren; Xuerui Ge; Xiaocong Chen (Aquatic Toxicology, 2026)

Effects of dietary serine addition to a high plant protein diet on growth performance, body composition, hepatosomatic histological structure and metabolism of taurine synthesis in juvenile turbot ( Scophthalmus maximus L.) - Guoshan Qi; Qinghui Ai; Xiaomin Jin; Ye Mu; Kangsen Mai; Muxiang Ge; Wenxiang Zhang; Hai Ren; Qinglin Wang (Journal of Fish Biology, 2026)
A feeding trial was carried out to investigate the effects of dietary serine on feeding, growth, biochemistry composition, hepatosomatic histological structure and metabolism of taurine synthesis in turbot ( Scophthalmus maximus L.) (2.0 ± 0.01 g) fed plant protein‐based diets. A fishmeal‐based control diet (DietFM) and another two isonitrogenous and isolipidic plant‐based diets containing 0.0% (DietPP) and 3.0% (DietS‐3%) serine were formulated and fed twice daily (06:30 and 18:30) to fish in triplicate groups for 9 weeks. Feed intake in fish fed DietS‐3% was notably higher than that in fish fed DietPP ( p p > 0.05). No significant difference ( p > 0.05) was found with the increase of dietary serine in final body weight, specific growth rate, weight gain rate, feed efficiency ratio, protein efficiency ratio and survival rate when a significant increase ( p p p > 0.05). A significant increase ( p p > 0.05) in fish fed DietS‐3% showed no obvious difference with those of fish fed DietPP ( p > 0.05). The cellular morphology and cell stripes in liver of fish fed diets with 3% serine inclusion were closer to that of fish fed DietFM. Considering the results, 3% serine supplementation in a high plant protein diet significantly increased feeding, mineral accumulation, body taurine content of turbot and obviously improved hepatosomatic histological structure. It is inferred that serine in a taurine‐deficient diet can probably convert to taurine to some degree in juvenile turbot, and the transformation differs with tissue distinction.

Comprehensive assessment and policy implications of pesticide packaging waste management in China - Wenjie Shangguan; Can Wang; Qiliang Huang; Zongjie Ren; Hongyi Liu; Chunli Xu; Ge Chen; Dukang Ma; Yongwang Guo; Lidong Cao (Waste Management, 2026)

Metabolic activation of pentachlorophenol: TCBQ as a potent inhibitor of gonadal steroidogenesis via 3β-hydroxysteroid dehydrogenase NAD+ binding-site thiolalkylation - Yao Lv; Jingwei Zhang; Ming Su; Shun Lu; Shaowei Wang; Ren-shan Ge; Huitao Li (Reproductive Toxicology, 2026)

Rapid starch degradation characterized by the related gene expression and key enzymes resulted in an optimum comprehensive quality of sugar, acid, and firmness in postharvest apples - Lingyu Qiu; Niu Ye; Yang Zhao; Mengke Cao; Miaomiao Ge; Xiaolin Ren; Yan Tang; Huiling Ma (Postharvest Biology and Technology, 2026)

Magnetic Fe-Mn spinel particle electrodes from red mud-shield slag wastes for 3D electrocatalytic dye degradation - Xinxin Li; Fumin Ren; Junshi Liu; Sibo Jia; Xiaoyu Ge; Houliang Guo (Journal of Environmental Management, 2026)

Recrystallization and orientation competition via hot extrusion in n-type Bi2Te3 alloys for advanced power generator - Tao Xiong; Hailong He; Ge Tian; Yi Wu; Youqun Li; Chunping Niu; Feng Jiang; Chenhao Ren; Mingzhe Rong (Chemical Engineering Journal, 2026)

Structural diversity of aldehydes determines covalent versus non-covalent inhibition mechanisms against steroid 5α-reductase type 1: Species-specific differences and preliminary structure-activity relationships - Junying Chen; Shufang Qi; Zijian Lin; Haonan Fang; Putian Zhang; Wanyu Li; Ren-shan Ge; Yiyan Wang (Chemico-Biological Interactions, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Trophic attenuation and transmission of antibiotic resistance in the aquatic food webs - Xue Xue; Shulun Jiang; You Ge; Yongjin Chen; Dongfa Gao; Long Ren; Zhen Kuang (Journal of Hazardous Materials, 2025)

Multiomic insights into the regulatory mechanism of anammox consortia: Interspecies cooperation, degradation and self-adaptation to plasticizer stress - Ge-Ge Wu; Jing-Ao Jin; Na-Na Han; Wen-Li Guo; Nian-Si Fan; Ren-Cun Jin (Journal of Hazardous Materials, 2025)

Thermodynamic, economic, and environmental analysis of a supercritical water partial oxidation autothermal cogeneration system of coal - Guowei Xing; Yifeng Li; Changyifan Ren; Zhiwei Ge; Liejin Guo (Journal of Cleaner Production, 2025)

Application of machine learning in soil fumigation remediation prediction and design - Qingli Han; Liqing Ge; Yuanchuan Ren; Youshun Yu (Journal of Environmental Chemical Engineering, 2025)

Machine learning intelligently selects feature values to construct a sensor array based on tri-functional Mn-doped covalent organic polymer nanozymes for identifying flavonoid compounds - Guo-Qi Zhang; Wen-Cai Jiang; Xiao-Mei Li; Ren-Jie Li; Yi Feng; Ri-Ge Li Nai; Hui-Lin Cheng; Zhi-Bo Hou; Xiao-Jun Luo; Yan Zhao (Food Chemistry, 2025)

Nonlinear rheological behavior and quantitative proteomic analysis of wheat aqueous phase protein at the air-water interface - Zhaoshi Chen; Ge Wang; Runkang Qiu; Peiyao Zhao; Hongjie Ren; Aijun Hu; Bei Fan; Liya Liu; Fengzhong Wang (Food Hydrocolloids, 2025)

Tracing copper pollution migration mechanisms in mine tailings pond and surrounding soils using Isotopes: A case study of the Shuimuchong tailings pond, Tongling, China - Mengxi Ren; Qikai Cai; Wenming Pei; Xu Gao; Junchao Ma; Ying Lu; Feng Ge; Xin Liu; Mingzhu Zhang; Keke Xu (Environmental Pollution, 2025)

Grass root microbiomes exhibit broader niche breadths but stronger phylogenetic clustering than forb root microbiomes in a temperate steppe - Ren Bai; An-Hui Ge; Meng Zhou; Wen-Hao Zhang; Wenming Bai (Plant and Soil, 2025)

SAFNet: a spatial adaptive fusion network for dual-domain undersampled MRI reconstruction - Yingjie Huo; Hongyuan Zhang; Dan Ge; Ziliang Ren (Physical and Engineering Sciences in Medicine, 2025)

DOM from eco-friendly fertilizers increases soil potential pathogen risk and shapes specific microbial populations under sprinkler and drip irrigation - Jinluo Fan; Rui Song; Heng Luo; Haijun Wu; Dongming Wu; Jun Wang; Yanqun Guo; Shuailing Hou; Mingguang Luo; Guoliang Ren; Hui Deng; Jiwei Luo; et al. (Applied Soil Ecology, 2025)

Inter‐Decadal Changes of Indian Ocean Dipole Around the Early 1980s and the Related Atmospheric and Oceanic Processes - Ge Song; Rongcai Ren (International Journal of Climatology, 2025)
This study demonstrates a significant inter‐decadal change of Indian Ocean Dipole (IOD) around the early 1980s and its connection to Pacific Decadal Oscillation (PDO). The changes of IOD include an initiation advancing and an increase in the occurrence of IOD events, particularly negative IOD events. Associated is an inter‐decadal strengthening of the coupling between IOD and sub‐surface IOD (Sub‐IOD) since the boreal spring season of IOD years. All these inter‐decadal changes coincide with the phase transition of PDO around the early 1980s, which has exerted its influence through atmospheric and oceanic pathways. On the one hand, negative/positive PDO forces easterly/westerly anomalies over the tropical Indian Ocean (TIO) by modulating Walker circulation, which is responsible for the increase in the occurrence of positive/negative IOD events. On the other hand, through the Indonesian Through Flow, PDO forced oceanic Rossby waves propagate westward from the Pacific to the Indian Ocean which contributes to deepening/shoaling the thermocline in the southwestern Indian Ocean. The inter‐decadal steepening of the TIO thermocline around the early 1980s, together with the strengthening of the surface westerly anomalies, gives rise to the strengthening of the vertical coupling between IOD and Sub‐IOD since the spring, which is mainly responsible for the inter‐decadal initiation advancing of IOD events. Though the initiation advancing of IOD events in the Coupled Model Inter‐comparison Project phase 6 (CMIP6) simulations is not as obvious as that in the reanalysis data, the linkage between positive PDO and the initiation advancing of negative IOD events also can be reproduced.

ESG Scores and financial performance are making energy companies be in a dilemma: evidence from China - Fang-rong Ren; Hui-yi Chen; Xi-ting Yang; Xin-ge Guan; Xiao-yan Liu (Environment, Development and Sustainability, 2025)

Bifidobacterium animalis subsp. Lactis A6 alleviates comorbid constipation and depression by rebalancing tryptophan metabolism - Jian Wang; Yimei Ren; Juan Chen; Shanbin Chen; Xiaoxia Li; Jianwen Chen; Xifan Wang; Lijun Li; Liang Zhao; Yixuan Li; Qi Zhang; Wei Xiong; et al. (Science Bulletin, 2025)

Isothiazolinone biocides as aromatase inhibitors: Hormonal disruption, and in silico docking and SAR/QSAR analysis - Shaowei Wang; Zhuoqi Chen; Xiya Ren; Chentao Ding; Xiulian Yang; Yunbing Tang; Ren-Shan Ge; Wei Chen; Yi Liu (Environmental Research, 2025)

MoO3-MoS2 with abundant oxygen vacancies for real-time seafood quality assessment - Guochen Qi; Shuwei Ren; Jingfang Ji; Hao Gao; Zhichuang Ma; Sufeng Fan; Pan Liu; Jingmin Ge (Chemical Engineering Journal, 2025)

Impact of mycotoxins on placental function: Focus on cyclopiazonic acid, deoxynivalenol, patulin, and zearalenone's metabolites - Huiqian Zhang; Xiuwei Shen; Jiayi He; Qingyuan Wang; Yunbing Tang; Peipei Pan; Ren-Shan Ge; Xiaoheng Li (Chemico-Biological Interactions, 2025)

Effects of altitude on light gasoline vehicles: fuel consumption and air pollution - Yanxu Ren; Wenhan Yu; Lijun Hao; Yunshan Ge (Atmospheric Pollution Research, 2025)

Optimizing blood–brain barrier permeability: the effect of wine processing on alkaloids in Phellodendri Chinensis Cortex - Shuo Zhang; Jiahui Zhao; Wenjing Ren; Yue Zhou; Yang Chen; Shiru Jiang; Gui Xu; Xiutong Ge; Hui Gao; Fan Zhang (Journal of Natural Medicines, 2025)

The role of endoplasmic reticulum stress in Atrazine-induced hepatic lipid accumulation - Honghao Qian; Shuping Ren; Haotang Zhao; Jingjing Shi; Zhili Ge; Jiaxin Zhang; Tianyou Wang; Xinyu Zhang; Huibin Jiang; Yuezhu Zhang; Lin Ye (Toxicology Letters, 2025)

Significant enhancement of inhibitory strength of bisphenol A analogs against human and rat 5α-reductase 1 upon halogenation of the benzene ring: Potentially disrupting neurosteroid biosynthesis - Shihan Wang; Shaowei Wang; Han Lu; Binbin Lu; Huitao Li; Yingfen Ying; Ren-shan Ge; Yunbing Tang (Toxicology and Applied Pharmacology, 2025)

A source-to-sink multiproxy analysis of late Eocene regional drainage evolution in the Beibuwan Basin of the South China Sea - Mingxuan Tan; Lianpu Sun; Mianpei Chen; Jiawang Ge; Ping Wang; Peigang Ren (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Preparation of novel p-n heterogeneous Ag2O/MnO2 composites and photocatalytic degradation of gaseous toluene - Yao Ge; Yi Ding; Ranran Cheng; Yenan Yang; Xuan Wu; Xinyu Jia; Qifang Ren (Journal of Environmental Chemical Engineering, 2025)

The adaptability of vegetation productivity to precipitation variability determines its resistance in central asian grassland ecosystems - Na Zeng; Xiaoli Ren; Zhongen Niu; Rong Ge (Journal of Arid Environments, 2025)

Effects of gallates on 5α-reductase type 1: structure-activity relationship and implications for neurosteroid balance in neuropsychiatric disorders - Putian Zhang; Wanyu Li; Xinmiao Lu; Shufang Qi; Haonan Fang; Junying Chen; Baiping Mao; Ren-shan Ge; Yiyan Wang (Chemico-Biological Interactions, 2025)

Organotins as inhibitors targeting human and rat steroid 5α-reductase 1: structure-activity relationship and docking analysis - Shufang Qi; Rong Cui; Wanyu Li; Jin Yang; Ke Zheng; Shaowei Wang; Ren-Shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2025)

Differential Settlement Control Between New and Existing Highway Subgrades in Silty Soils - Jian Zhang; Feng Hu; Qiang Gao; Kuo Zhang; Chuanxiao Liu; Junhao Ge; Zhe Ren; Guangtan Cheng (Geotechnical and Geological Engineering, 2025)

12-ethoxy-Marchantin A, a new macrocyclic bis-bibenzyl from Marchantia polymorpha L., exerts anti-aging activity through activating MAPKs-dependent Nrf2/HO-1 signaling pathways - Bingjian Wu; Ge Ge; Jiaxin Xu; Yi Xing; Kun Hu; Jie Ren; Jia Yang (Biogerontology, 2025)

Structure-activity relationships of halogenated disinfectants as potent inhibitors of 5α-reductase type 1: Potential impact on neurosteroid synthesis - Haonan Fang; Wanyu Li; Xinmiao Lu; Junying Chen; Putian Zhang; Shufang Qi; Ren-shan Ge; Yiyan Wang (Journal of Hazardous Materials, 2025)

Biobased reversible acid-sensitive colorimetric fabric sensor based on natural polyphenols and amino acid - Xiao Ren; Haixia Jiang; Jing Cao; Jinyun Wu; Fengyan Ge (Chemical Engineering Journal, 2025)

Neutron resonance integral analysis of 238U within resolved resonance region - Yufei Pan; Jimin Wang; Ruirui Xu; Xi Tao; Yue Zhang; Jie Ren; Yuan Tian; Zhigang Ge; Nengchuan Shu; Kang Xing; Xiaofei Wu (Annals of Nuclear Energy, 2025)

Isolation and characterization of a marine strain: Bacillus inaquosorum, and its feeding effects on Sebastes schlegelii as feed additive - Xin-Kun Zhu; Ren-Ge Hu; Wei Cong; Yuan-Huan Kang; Li-Yan Wang; Tao Yang; Shu Li (Aquaculture, 2025)

Application of biochar in saline soils enhances soil resilience and reduces greenhouse gas emissions in arid irrigation areas - Shixiong Ren; Jiawang Zhong; Kai Wang; Rong Liu; Hao Feng; Qin’ge Dong; Yuchen Yang (Soil and Tillage Research, 2025)

Relationship between internal void ratio and morphological parameters of carbonate sand - Yan Qian; Yuedong Wu; Yuzhe Ren; Yi Pik Cheng; Abraham C.F. Chiu; Jian Liu; Tiange Ge (Computers and Geotechnics, 2025)

Neonicotinoid pesticides: residue detection and dietary risk assessment in commercially available plant-based agricultural products in North China - Peng Sun; Danqi Ren; Guotao Ding; Ning Hao; Ge Shi; Weihao Li (Environmental Monitoring and Assessment, 2025)

Quorum sensing-mediated microecological homeostasis in anammox consortia - Jia-Hui Yang; Dong-Qi Huang; Ge-Ge Wu; Na-Na Han; Nian-Si Fan; Ren-Cun Jin (Journal of Hazardous Materials, 2025)

Differential size-dependent response patterns and antibiotic resistance development mechanism in anammox consortia - Na-Na Han; Jun-Hui Yang; Ge-Ge Wu; Jia-Hui Yang; Jing-Ao Jin; Nian-Si Fan; Ren-Cun Jin (Journal of Hazardous Materials, 2025)

Rapid cross-linking of MoS2 photothermal layers and their assembly of interface evaporators for desalination and environmental optimization - Zekun Zhang; Xiuling Li; Guangqi Liu; Shuo Qi; Jing Lv; Bo Ge; Tonghui Zhang; Guina Ren; Zhaozhu Zhang (Desalination, 2025)

Study of enhanced nitrogen removal performance and mechanism of iron-modified activated carbon in low-temperature environments - Guangtao Li; Jinlong Han; Yunchang Wang; Shihong Wu; Liyan Ge; Xueqian An; Xiaoyang Liu; Wenfang Gao; Li Sun; Zhijun Ren; Kengo Kubota (Journal of Environmental Chemical Engineering, 2025)

Pyridine-based ionic liquid with Sn site as an efficient catalyst for CO2 cycloaddition - Wenyu Ge; Shuai Zheng; Dongyu Jin; Yuming Tu; Chencan Du; Zhongqi Ren (Chemical Engineering Journal, 2025)

Invasion of Spartina species enhance blue carbon functions by increasing CO2 uptake and reducing methane emissions in Chinese and Danish coastal wetlands - Ming Ge; Linjing Ren; Dan Yang; Xiuzhen Li; Ying Huang; Jianwu Tang; Hans Brix (Journal of Cleaner Production, 2025)

Inheritance or Recruitment? The Assembly Mechanisms and Functional Dynamics of Microbial Communities in the Life Cycle of a Wood‐Feeding Beetle - Si‐Xun Ge; Yi‐Ming Niu; Li‐Li Ren; Shi‐Xiang Zong (Molecular Ecology, 2025)
Microbial partners enhance the metabolic capabilities of insects, enabling their adaptation to diverse ecological niches. Xylophagous insects have larvae that can digest lignocellulose and cope with plant secondary metabolites (PSMs). However, there is little information in terms of microbiome sources, dynamics and species contributions. This limits our understanding of the interaction between xylophagous insects and the microbiome. Monochamus saltuarius (Cerambycidae) is a significant borer of conifers. We used combined qPCR, host genomic and microbiome metagenomic datasets, as well as in vitro validation experiments to study the dynamics of the associated microbiome and its interactions with M. saltuarius . We evaluated microbial metabolic/biosynthetic contributions and validated their related functions. Our findings revealed that insect growth and development altered the quantity and community composition of associated bacteria and fungi. The egg microbiome was particularly susceptible to alteration due to oviposition pits. Bacterial transmission largely persisted between developmental stages, while fungal re‐acquisition primarily originated from the external environment. By reconstructing community pathway maps, we identified the cooperative interactions between the insect and its gut microbiome. As larvae transitioned from phloem to xylem feeding, the functional role of the gut microbiome in various pathways was weakened. Remarkably, high‐contribution bacterial species largely overlapped across different functional roles, and these species also showed considerable overlap between phloem and xylem feeding periods. Overall, our study highlights the unique interaction between xylophagous insects and their microbiome, which enhances their ability in lignocellulose digestion, PSMs degradation and the acquisition of essential amino acids, as well as vitamins.

Optimization and identification of key process parameters for in-situ leaching of uranium in the Barun uranium deposit, China - Peng Qiao; Yuanqing Fan; Shengqing Xiong; Liangquan Ge; Yixuan Yao; Ruyi Wang; Hao Song; Huijie Yu; Xiaoping Ren; Zengjie Gui (Ore and Energy Resource Geology, 2025)

Efficient preparation of potassium humate from waste vegetable leaves: Development of a Cu2O@HAK catalyst and innovative application of hydrothermal method - Jiamin Qi; Jiliang Zheng; Yatang Dai; Bo Yang; Haohao Bian; Xinyu Chen; Shunyu Yin; Xiuling Yan; Xiaoyan He; Hongguang Zhao; Yanjie Ren; Changchun Ge; et al. (Journal of Environmental Chemical Engineering, 2025)

Identification and spatial distribution of organophosphorus flame retardants in surface soils from typical petrochemical industry and flame retardant production parks in China - Zhiyong Fan; Chaoyang Long; Xiang Ge; Zhaofa Huang; Helong Ren; Yingxin Yu; Taicheng An (Environmental Pollution, 2025)

Analysis of Increased False-Positive ELISA Results for HIV in the Blood of Donors Infected with SARS-CoV-2 - H. Lin; Z. Wang; Q. Ren; Z. Cai; F. Ge; W. Yuan; T. Liao; Y. Wu; R. Peng; Y. Gu; Y. Kuang (Bulletin of Experimental Biology and Medicine, 2025)

Integrated metabolomic and transcriptomic analysis reveals the regulatory effects of IAA on polyphenol biosynthesis and antioxidant activity in Phlebopus portentosus - Taobo Xiang; Feng Ge; Lei Zhu; Gaige Shao; Tao Wu; Hao Fan; Yueqian Liu; Longyu Wang; Jing Wang; Peng Li; Qin He; Ailiang Jiang; et al. (Food Bioscience, 2025)

Urinary neonicotinoid exposure and its association with hypertension and dyslipidemia among the elderly: A cross-sectional study in Shenzhen, China - Xinxin Tang; Jiaojiao Ma; Peiyi Liu; Sisi Yu; Xiaohu Ren; Wenchao Zhu; Xiao Chen; Yiming Ge; Haiyan Huang; Jianjun Liu; Shaoyou Lu (Chemosphere, 2025)

Pseudorabies virus inhibits the unfolded protein response for viral replication during the late stages of infection - Peng Gao; Jianle Ren; Qiongqiong Zhou; Peng Chen; Ailin Zhang; Yongning Zhang; Lei Zhou; Xinna Ge; Xin Guo; Jun Han; Hanchun Yang (Veterinary Microbiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Dopamine-supported HPLC post-column derivatization to fluorescence: Simultaneous and sensitive detection of eight tea polyphenols - Hongchen Li; Jing Cheng; Hanbing Ge; Jingbo Sun; Zihan Chen; Jiali Ren; Yi Du; Dong Xu; Zhiqin Yuan (Food Chemistry, 2025)

The short-term comprehensive impact of the phase-out of global coal combustion on air pollution and climate change - Wendong Ge; Noah S. Prime; Steven J. Smith; Junfeng Liu; Yang Ren; Yuhan Zhou; Huihuang Wu; Xian Wang; Gang Chen (Environmental Pollution, 2025)

Winter wheat identification in China through FY-3D NDVI&EVI satellite data and DNN Fusion - Fangmin Zhang; Xiaofei Wang; Ge Gao; Zuguang Ren; Kaidi Zhang (International Journal of Remote Sensing, 2025)

Occurrence and ecological risks of organophosphate esters in the sediments of Hangzhou Bay and the East China Sea - Peng Zhang; Yaqing Cui; Ren Shi; Jing Wang; Linke Ge; Qinglin Mu (Marine Pollution Bulletin, 2025)

Corrigendum to “Inhibitory effects of parabens on human and rat 17β-hydroxysteroid dehydrogenase 1: Mechanisms of action and impact on hormone synthesis” Toxicology 506 (August) (2024) 153873 - Zhuoqi Chen; Chaochao Gong; Yunbing Tang; Yang Zhu; Shaowei Wang; Ren-shan Ge; Yingfen Ying (Toxicology, 2025)

In-situ monitoring of clamp-repair-induced displacements in the submarine pipeline using a MEMS accelerometer array: A sea trial - Xueyu Ren; Jiawang Chen; Peng Zhou; Zhangyong Jin; Han Ge; Yulin Si; Yiyuan Zhang; Xiaoqing Peng; Xuehua Chen; Yunchao Peng (Ocean Engineering, 2025)

Spatiotemporal distribution prediction for PM2.5 based on STXGBoost model and high-density monitoring sensors in Zhengzhou High Tech Zone, China - Shiqi Zhao; Hong Lin; Hongjun Wang; Gege Liu; Xiaoning Wang; Kailun Du; Ge Ren (Journal of Environmental Management, 2025)

Spatio-temporal coupling coordination analysis between local governments' environmental performance and listed companies' ESG performance - Xia Wu; Chunxu Hao; Yuhan Li; Chazhong Ge; Xianming Duan; Jing Ren; Cong Han (Environmental Impact Assessment Review, 2025)

Microalgae: A good carrier for biological selenium enrichment - Shuang Liu; Muhammad Abu Bakar Saddique; Yiming Liang; Ge Guan; Haotian Su; Beibei Hu; Songqi Yang; Xiumei Luo; Maozhi Ren (Bioresource Technology, 2025)

Paraben preservatives exhibit inhibition on human and rat steroid 5α-reductase 1: A comprehensive 3D-QSAR and computational analysis - He Zhu; Chentao Ding; Yunbing Tang; Jingyi Zheng; Shaowei Wang; Zhongyao Ji; Yang Zhu; Ren-shan Ge; Huitao Li (Journal of Hazardous Materials, 2024)

Closed-loop recycling of biodegradable poly(butylene adipate-co-terephthalate) based on hydrolysis and repolymerization strategy - Wei-Zhen Zheng; Xiao Li; Jing Xie; Ze-Yang Zhang; Ping-Li Wang; Dan Huang; Zhong-Lai Ren; Jun-Hui Ji; Ge-Xia Wang (Journal of Environmental Chemical Engineering, 2024)

Site selection and effects of background towers on urban CO2 estimates: A case study from central downtown Zhengzhou in China - Ge Ren; Kailun Du; Anna Karion; Shiqi Zhao; Israel Lopez-Coto; Xiaoning Wang; James Whetstone; Hong Lin (Environmental Research, 2024)

Co-exposure to parabens, bisphenol A, and triclosan and the associations with dyslipidemia in Chinese older adults: The mediation effect of oxidative stress - Zhihui Guo; Xiaohu Ren; Peiyi Liu; Yilan Deng; Junye Bian; Yiming Ge; Benhong Xu; Xinxin Tang; Xinjie Li; Haiyan Huang; Jianjun Liu; Shaoyou Lu (Environmental Research, 2024)

Spatial heterogeneity of volatile organic compound pollution in a typical industrial park based on multi-point online monitoring: Pollution characteristics, health risks, and priority-controlled species - Mengjuan Han; Ge Ren; Xinna Zhao; Xiaodong Zhang; Hong Lin; Dan Liu; Lei Wang (Atmospheric Environment, 2024)

Structural determinants of parabens in inhibiting human and rat gonadal 3β-hydroxysteroid dehydrogenase - Chentao Ding; He Zhu; Yunbing Tang; Yingfen Ying; Yang Zhu; Han Lin; Ren-Shan Ge; Huitao Li (Toxicology and Applied Pharmacology, 2024)

Temperature changes of the Mid-Late Holocene transition in North China and their implications for regional cultural succession - Jiheng Shi; Shude Ren; Manyue Li; Can-Ge Li; Lili Song; Qinghai Xu; Shengrui Zhang (Quaternary Science Reviews, 2024)

Unveiling the pathogenic and multidrug-resistant profiles of Vibrio alfacsensis: A potential identified threat in turbot (Scophthalmus maximus) aquaculture - Ren-Ge Hu; Lei Yang; Li-Yan Wang; Yu-Lin Yang; Hong-Jin Li; Bin-Tong Yang; Yuan-Huan Kang; Zhen-Lin Liang; Wei Cong (Journal of Hazardous Materials, 2024)

CBS/CSE mediated H2S production induced AMPs expression through Toll pathway in crabs with black gill syndrome - Ziyue Zhu; Xingkong Ma; Xiaohan Liu; Liangmin Zheng; Lihua Zhang; Xiaoling Dai; Hao Li; Zhaoqian Zhang; Bingyan Wang; Xin Huang; Jiachun Ge; Qian Ren (Fish & Shellfish Immunology, 2024)

Metagenomic analysis unveiled the response of microbial community and antimicrobial resistome in natural water body to duck farm sewage - Chang Fang; Kai-di Liu; Feng-jie Tian; Jin-ying Li; Si-jie Li; Rong-min Zhang; Jian Sun; Liang-xing Fang; Hao Ren; Min-ge Wang; Xiao-ping Liao (Environmental Pollution, 2024)

ATP-activated Fe(Ⅲ)/carbon dots assemblies for in situ generating nanozyme and simultaneously monitoring tumor cell ferroptosis - Jian Li; Jian Wang; Ke Liang; Xiaokuang Xue; Tiejin Chen; Zekun Gao; Haohui Ren; Lizeng Gao; Jiechao Ge (Chemical Engineering Journal, 2024)

Identification and quantification of reactive species in aqueous medium during application of advanced oxidation processes: A critical review - Wenjing Li; Ge Song; Jiana Jing; Xueying Ren; Chaohui Zhang; Mehmet A. Oturan; Minghua Zhou (Chemical Engineering Journal, 2024)

Inhibition of human and rat placental 3β-hydroxysteroid dehydrogenases by bisphenol A analogues depends on their hydrophobicity: In silico docking analysis - Shaowei Wang; Han Lu; Yingna Zhai; Yunbing Tang; Ming Su; Huitao Li; Yiyan Wang; Yi Liu; Ren-shan Ge (Chemico-Biological Interactions, 2024)

Investigation of γ-polyglutamic acid production via asynchronous saccharification and fermentation of raw corn starch - Yutao Gou; Chenxin Niu; Fanglan Ge; Wei Li; Guiying Cheng; Shuai Jing; Hong Yang; Jiao Li; Yao Ren (World Journal of Microbiology and Biotechnology, 2024)

Investigate the optimum design of atomizing nozzles for coal dust suppression by using multifactor level response surface methodology - Shuaishuai Ren; Deji Jing; Shaocheng Ge; Yinuo Chen; Ping Chang (Process Safety and Environmental Protection, 2024)

The morphological research of ZnxCd1-xS based photocatalysts for energy conversion - Xiuzhen Zheng; Jingbiao Ge; Linfeng Ye; Yang Yang; Jiahui Wang; Wei Ren; Sugang Meng; Shifu Chen (Journal of Environmental Chemical Engineering, 2024)

Polybrominated diphenyl ethers and their alternatives in soil cores from a typical flame-retardant production park: Vertical distribution and potential influencing factors - Chifei Bai; Xiang Ge; Zhaofa Huang; Zenghua Qi; Helong Ren; Yingxin Yu; Taicheng An (Environmental Pollution, 2024)

Promoting adsorption-diffusion-deposition of Zn2+ via a highly reactive modulator for dendrite-free and kinetics-enhanced Zn metal anode - Yilun Ren; Haifeng Bian; Shaozhong Chang; Yujie Ma; Hao Wu; Qing Zhou; Shunshun Jia; Ge Xue; Jian Gu; Haiming Lu; Xiangkang Meng (Chemical Engineering Journal, 2024)

Smart contact Lenses: From rational design strategies to wearable health monitoring - Fei Han; Ping Ge; Fei Wang; Yanshen Yang; Shumeng Chen; Jing Kang; Yuan Ren; Hao Liu; Zhao Wei; Yuan He; Feng Xu (Chemical Engineering Journal, 2024)

A hollow mesoporous iron oxide nanoparticle to strengthen Fenton reaction and weaken antioxidant defense systems for high efficacy tumor ferroptosis therapy - Jing Yang; Jiaoyang Zhu; Bin Ren; Haobin Cai; Zongheng Li; Qingdeng Fan; Wei Xiong; Jie Feng; Chenggong Yan; Ge Wen; Yan Li; Chaomin Chen; et al. (Chemical Engineering Journal, 2024)

Food additive salicylates inhibit human and rat placental 3β-hydroxysteroid dehydrogenase: 3D-QSAR and in silico analysis - Xiulian Yang; Shaowei Wang; Yunbing Tang; Yingfen Ying; Yang Zhu; Congde Chen; Ren-shan Ge; Miaoqing Liu (Chemico-Biological Interactions, 2024)

Nitrogen-doped MoS2 QDs as fluorescent probes for sensitive detection of curcumin and cell imaging - Jia Ge; Zhiyao Zhai; Yuru Chen; Zhaohui Li; Hongfen Yang; Ren Cai (Analytica Chimica Acta, 2024)

Improving the sustainability of milk production across different climate regions in China - Zhaoping Wu; Yuanyuan Du; Guofu Yang; Linshan Lin; Xiaoyu Hou; Yandong Tan; Xing Fan; Yuan Ren; Bijie Wu; Shun Liu; Scott X. Chang; Wanhong Sun; et al. (Sustainable Production and Consumption, 2024)

Effects of straw management and N levels on gross nitrogen transformations in fluvo-aquic soil of the North China Plain - Guocui Ren; Xianfeng Zhang; Jinbo Zhang; Lan Mu; Xiuli Xin; Yiming Yun; Anning Zhu; Shuchun Ge (Science of The Total Environment, 2024)

Beta-blocker drives the conjugative transfer of multidrug resistance genes in pure and complex biological systems - Qian Wu; Ge-Ge Wu; Kai-Nan Pan; Xue-Ping Wang; Hong-Yan Li; Zhe Tian; Ren-Cun Jin; Nian-Si Fan (Journal of Hazardous Materials, 2024)

Bismuth oxychloride-sodium alginate hydrogel derived interface desalination solar evaporator for environmental remediation - Xiuling Li; Yangyang Peng; Yanan Pang; Bo Ge; Limin Zhao; Tonghui Zhang; Guina Ren; Zhaozhu Zhang (Chemical Engineering Journal, 2024)

Inhibitory effects of parabens on human and rat 17β-hydroxysteroid dehydrogenase 1: Mechanisms of action and impact on hormone synthesis - Zouqi Chen; Chaochao Gong; Yunbing Tang; Yang Zhu; Shaowei Wang; Ren-shan Ge; Yingfen Ying (Toxicology, 2024)

Research on measurement and control system of deep-sea self-contained static cone penetration probe - Peng Zhou; Junrong Chen; Hang Zhou; Ziqiang Ren; Zhenwu Yu; Yongqiang Ge; Zhonghui Zhou; Jianling Zhou; Yulin Si; Jiawang Chen (Ocean Engineering, 2024)

Comparative study of organic removal by pre-adsorption oxidation and synchronous adsorption oxidation processes: Performance and mechanism - Bo Tan; Ge Gou; Yi Ren; Zhuoyao Fang; Chao Liu; Bo Lai; Naiwen Li; Jun Li (Journal of Hazardous Materials, 2024)

Removal and assessment of cadmium contamination based on the toxic responds of a soil ciliate Colpoda sp. - Weibin Zheng; Sen Hou; Ying Chen; Chang Ge; Bing Ni; Xiaodan Zheng; Hongbo Chen; Tianyi Zhao; Aijie Wang; Nanqi Ren (Journal of Hazardous Materials, 2024)

Microstructure regulation of Zn0.5Cd0.5S for enhancing the photocatalytic H2 production - Yang Yang; Wei Ren; Jiahui Wang; Xiuzhen Zheng; Jingbiao Ge; Sugang Meng; Shifu Chen; Chun Cai (Fuel, 2024)

Response characteristics of plants and pollutant removal in subsurface flow constructed wetlands under resting operation - Jingying Zhang; Hongli Xie; Ge Bai; Dun Guo; Lei Yang; Jun Lan; Yongxiang Ren (Chemical Engineering Journal, 2024)

Akkermansia muciniphila Protects Against Antibiotic-Associated Diarrhea in Mice - Shenyin Liu; Suying Zhao; Zhiwei Cheng; Yilin Ren; Xinyi Shi; Jing Mu; Xiangyang Ge; Yuan Dai; Lei Li; Zhan Zhang (Probiotics and Antimicrobial Proteins, 2024)

The evaluation of bacteriophage therapy in aquaculture: A systematic review and meta-analysis - Lei Yang; Qing Yang; Ren-Ge Hu; Wei Cong; Shu Li; Yuan-Huan Kang (Aquaculture, 2024)

UV-filter benzophenones suppress human, pig, rat, and mouse 11β-hydroxysteroid dehydrogenase 1: Structure-activity relationship and in silico docking analysis - Ting Hao; Xin Zhao; Zhongyao Ji; Miaomiao Xia; Han Lu; Jianmin Sang; Shaowei Wang; Linxi Li; Ren-shan Ge; Qiqi Zhu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

The properties of plant-based protein particles with co-spray drying agents - Zhe Liu; Yanzheng Ge; Shanshan Li; Chao Wu; Xue Hei; Guangyue Ren; Benu Adhikari; Qiang Wang; Aimin Shi (Journal of Food Engineering, 2024)

Construction of CuFe2O4/Bi2MoO6 heterogeneous catalyst for high-efficiency photocatalytic degradation of levofloxacin under visible light: Mechanism, pathways and DFT calculation - Xinyu Jia; Shilong Xu; Qinglin Huang; Haixia Ji; Yao Ge; Yenan Yang; Qifang Ren; Shaohua Chen; Zhen Jin; Yi Ding (Journal of Environmental Chemical Engineering, 2024)

A novel PVI-PVA/PS composite membrane modified by metal ions for CO2 separation: Effect and mechanism - Yuming Tu; Dongyu Jin; Wenyu Ge; Lei Xu; Chencan Du; Zhiyong Zhou; Zhongqi Ren (Journal of Environmental Chemical Engineering, 2024)

Environmental adaptation, growth performance and nutrient content of the clam Cyclina sinensis from different geographic locations - Shiyu Yan; Qing Xia; Zhenquan Cui; Guoliang Ren; Xiaoying Li; Hongxing Ge; Meimei Liu; Zhiguo Dong (Frontiers in Marine Science, 2024)
The clam Cyclina sinensis is an economically important marine species in China. However, overfishing, habitat destruction, and inbreeding have led to the destruction of genetic resources. In this study, five natural populations [Dandong (DD), Dongying (DY), Tianjin (TJ), Wenzhou (WZ), and Yancheng (YC)] from different geographical locations were relocated and cultured homogeneously to study their potential for translocation and environmental adaptation by observing growth performance and nutrient content. There were significant differences in the growth rates of shell length (SL), shell height (SH), and shell width (SW) among the five populations ( P<0.05 ). The DD, TJ, and YC populations exhibited the highest SL and SH growth rates, whereas these were lowest in the WZ population. The survival rate was highest in the YC population and lowest in the WZ population, which was significantly lower than the other four populations ( P<0.05 ). The DD population exhibited superior plumpness and glycogen content, and the overall glycogen content in male C. sinensis was higher compared with that in females ( P<0.05 ). All populations displayed a high total amino acid content and the essential amino acid/Total Amino Acid (EAA/TAA) and Non-essential amino acid/Total Amino Acid (NEAA/TAA) ratios in the soft tissue of all five populations aligned with the FAO/WHO ideal protein evaluation standards. Despite the same aquaculture environment, however, the nutrient composition of C. sinensis sampled from different populations varied significantly ( P<0.05 ).Therefore, ex situ conservation did not eliminate nutritional differences between the different populations of C. sinensis. These findings highlight the importance of considering environmental and ecological factors in the nutritional assessment and cultivation of shellfish. In addition, C. sinensis from sampling sites closer to the transplantation sites had higher survival rates and growth rates, and the gonadal development of all populations showed adaption to the local environment, resulting in synchronization of the reproductive period.

The metabolic activation of pentachlorophenol to chloranil as a potent inhibitor of human and rat placental 3β-hydroxysteroid dehydrogenases - Weibing Zhang; Ming Su; Hao Lin; Chengshuang Pan; Yunbing Tang; Ren-shan Ge; Qianjin Fei (Toxicology Letters, 2024)

Structure-activity relationship and mechanistic study of organotins as inhibitors of human, pig, and rat gonadal 3β-hydroxysteroid dehydrogenases - Peiyu Wang; Zhongyao Ji; Huiqian Chen; Sailing Chen; Chengshuang Pan; Qianjin Fei; Ren-shan Ge; Ping Duan; Linxi Li (Toxicology and Applied Pharmacology, 2024)

Differential inhibition of sildenafil and macitentan on saxagliptin metabolism - Ge-xin Dai; Wei Tan; Yuxin Shen; Dongdong Lin; Ren-ai Xu; Qianmeng Lin; Zhen Wei (Toxicology and Applied Pharmacology, 2024)

Calcium-based polymers for suppression of soil acidification by improving acid-buffering capacity and inhibiting nitrification - Fei Kang; Yunshan Meng; Yanning Ge; Yun Zhang; Haixiang Gao; Xueqin Ren; Jie Wang; Shuwen Hu (Journal of Environmental Sciences, 2024)

A self-floating graphite felt evaporator: Interface wetting control and its application in environmental remediation and desalination - Zekun Zhang; Yujiao Luo; Mingyang Li; Bo Ge; Limin Zhao; Tonghui Zhang; Guina Ren; Zhaozhu Zhang (Chemical Engineering Journal, 2024)

Carbon-chain length determines the binding affinity and inhibitory strength of per- and polyfluoroalkyl substances on human and rat steroid 5α-reductase 1 activity - Rong Cui; Lei Ye; Xinyi Qiao; Shaowei Wang; Ke Zheng; Jin Yang; Ren-shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Based on historical weather data to predict summer field-scale maize yield: Assimilation of remote sensing data to WOFOST model by ensemble Kalman filter algorithm - Shixiong Ren; Hao Chen; Jian Hou; Peng Zhao; Qin'ge Dong; Hao Feng (Computers and Electronics in Agriculture, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Development of eco-friendly and robust structural materials via binder-free lamination of waste biomass with help of finite element method - Quanliang Wang; Longxiao Zhu; Min Wang; Liping Cai; Haoran Ye; Zhongfeng Zhang; Yi Ren; Yang Yang; Chunxia Chen; Shengbo Ge; Wentao Gan (Journal of Cleaner Production, 2024)

Enhanced mixed flotation of copper–molybdenum ore using dodecyl dimethyl betaine-emulsified kerosene as environmentally friendly collector - Wencheng Ge; Jie Liu; Hui Ren; Yimin Zhu; Wenjie Han; Yuexin Han (Journal of Cleaner Production, 2024)

Demethoxylation of curcumin enhances its inhibition on human and rat 17β-hydroxysteroid dehydrogenase 3: QSAR structure-activity relationship and in silico docking analysis - Zhongyao Ji; Jianmin Sang; Hong Wang; Miaomiao Xia; Ting Hao; Liping Chen; Han Lu; Shaowei Wang; Ming Yao; Linxi Li; Ren-shan Ge (Food and Chemical Toxicology, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

Heterologous expression of taxane genes confers resistance to fall armyworm in Nicotiana benthamiana - Zhenlu Xu; Yaohua Zhai; Huimin Chang; Da Yan; Pengliang Ge; Guangming Ren; Lijun Zhang; Ye Yuan; Ruoyan Wang; Wentao Li; Fuguang Li; Maozhi Ren; et al. (Plant Cell Reports, 2024)

Research on anchoring force of the deep-sea stratum drilling robot - Peihao Zhang; Jiawang Chen; Yongqiang Ge; Xingshuang Lin; Xiaoling Le; Zixin Weng; Ziqiang Ren (Marine Georesources & Geotechnology, 2024)

Enhanced inhibition of human and rat aromatase activity by benzene ring substitutions in bisphenol A: QSAR structure-activity relationship and in silico docking analysis - Jingyi Zheng; Sailing Chen; Han Lu; Miaomiao Xia; Shaowei Wang; Xiaoheng Li; Huitao Li; Yiyan Wang; Ren-shan Ge; Yi Liu (Journal of Hazardous Materials, 2024)

Application of temperature-sensitive liquid embolic agent loaded with oxaliplatin in the TACE procedure for rabbit VX2 gastric cancer - Yahua Li; Xiaoyong Ge; Zongming Li; Zihe Zhou; Kunpeng Wu; Yifan Li; Tengfei Ji; Changran Wang; Kefeng Guo; Jianzhuang Ren; Xinwei Han; Kewei Ren (Drug Delivery and Translational Research, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Improvement of non-specific immunity, intestinal health and microbiota of crucian carp (Carassius auratus) juvenile with dietary supplementation of Bacillus coagulans BC1 - Ren-Ge Hu; Bin-Tong Yang; Zi-Yan Zheng; Zhen-Lin Liang; Yuan-Huan Kang; Wei Cong (Aquaculture, 2024)

Measurement of perfluoroalkyl substances in drinking water sources by DGT sampler with a novel fluorinated graphite binding gel - Fan Dong; Fan Ge; Xinting Zhao; Daming Sun; Suyu Ren; Yan Wang; Feng Tan (Science of The Total Environment, 2024)

Nonlinear effect of NOx concentration decrease on secondary aerosol formation in the Beijing-Tianjin-Hebei region: Evidence from smog chamber experiments and field observations - Junling Li; Tianzeng Chen; Hao Zhang; Yongcheng Jia; Yangxi Chu; Yongxin Yan; Haijie Zhang; Yanqin Ren; Hong Li; Jingnan Hu; Weigang Wang; Biwu Chu; et al. (Science of The Total Environment, 2024)

Research and development of vortex suction dedusting device based on multi-factor horizontal response surface method - Shuaishuai Ren; Deji Jing; Shaocheng Ge; Mingxing Ma; Mohammad Waqar Ali Asad; Ping Chang (Journal of Cleaner Production, 2024)

Catalytic gasification of anthracene in supercritical water with Ni/TiO2 catalyst: Products distribution and kinetics - Fanrui Meng; Shenghui Guo; Shi Liu; Changyifan Ren; Xingang Qi; Hui Jin; Zhiwei Ge; Liejin Guo (Fuel, 2024)

Chalcones from plants cause toxicity by inhibiting human and rat 11β-hydroxysteroid dehydrogenase 2: 3D-quantitative structure-activity relationship (3D-QSAR) and in silico docking analysis - Hang Lin; Ming Su; Chao Wen; Yunbing Tang; Huitao Li; Yandan Wu; Ren-shan Ge; Xing-wang Li; Han Lin (Food and Chemical Toxicology, 2024)

Unraveling the electrical energy loss in silver nanowire electrodes for flexible and Large-Area organic solar cells - Hao Ren; Wei-Shuo Chen; Jing-De Chen; Jin-Peng Yang; Ye-Fan Zhang; Hong-Yi Hou; Shuo Tian; Heng-Ru Ge; Yan-Qing Li; Jian-Xin Tang (Chemical Engineering Journal, 2024)

Impacts of coal use phase-out in China on the atmospheric environment: (2) public health and global radiative forcing - Yuhan Zhou; Jie Li; Wendong Ge; Junfeng Liu; Huihuang Wu; Leyi Zheng; Xian Wang; Yue Qin; Jingcheng Zhou; Yuqing Wang; Yang Ren (Atmospheric Environment, 2024)

The crosstalk between Toll and AMPK signaling pathways mediates growth inhibition of Eriocheir sinensis under deltamethrin stress - Qian Ren; Ximei Nie; Xingkong Ma; Zhengxiao Han; Yanfang Li; Xintong Yang; Lei Ji; Rongqian Su; Jiachun Ge; Xin Huang (Aquatic Toxicology, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Vitamin C enhances the sensitivity of osteosarcoma to arsenic trioxide via inhibiting aerobic glycolysis - Ying Liu; Jinrui Yue; Zijing Ren; Mingyu He; Ao Wang; Jiajie Xie; Tao Li; Guoxin Liu; Xuting He; Shiyu Ge; Ye Yuan; Lei Yang (Toxicology and Applied Pharmacology, 2024)

Distribution, sources and ecological risks of per- and polyfluoroalkyl substances in overlying water and sediment from the mangrove ecosystem in Hainan Island, China - Guoliang Ren; Like Chen; Jinluo Fan; Shuailing Hou; Junnan Chen; Hui Deng; Jiwei Luo; Peng Huang; Yuanyuan Zhao; Jiatong Li; Dan Feng; Chengjun Ge; et al. (Science of The Total Environment, 2024)

Bisphenol a alternatives suppress human and rat aromatase activity: QSAR structure-activity relationship and in silico docking analysis - Miaomiao Xia; Jingyi Zheng; Sailin Chen; Yunbing Tang; Shaowei Wang; Zhongyao Ji; Ting Hao; Huitao Li; Linxi Li; Ren-shan Ge; Yi Liu (Food and Chemical Toxicology, 2024)

Efficient degradation of ciprofloxacin in wastewater by CuFe2O4/CuS photocatalyst activated peroxynomosulfate - Xinyu Jia; Jinhui Zhang; Qinglin Huang; Chunyu Xiong; Haixia Ji; Qifang Ren; Zhen Jin; Shaohua Chen; Wanmi Guo; Jing Chen; Yao Ge; Yi Ding (Environmental Research, 2024)

Band-division utilization of core-shell photocatalyst under condenser solar-light and enhancement of synergistic catalytic CO2 reduction - Ke Wang; Yuqi Ren; Nan Wang; Miao Cheng; Jiancheng Zhou; Yang Ge; Naixu Li (Chemical Engineering Journal, 2024)

Arbutin inhibits androgen biosynthesis by rat immature Leydig cells in vitro - Yuanyuan Shan; Yang Yu; Xiaoheng Li; Qiqi Zhu; Yiyan Wang; Zhiguang Zhao; Ren-Shan Ge (Reproductive Toxicology, 2023)

Community diversity and co-occurrence patterns of keratinophilic microorganisms in hospital garden soils - Yulian Ren; Zhiyuan Zhang; Chunbo Dong; Wei Ge; Zongqi Liang; Yanfeng Han (Pedobiologia, 2023)

Nightmare or delight: Taxonomic circumscription meets reticulate evolution in the phylogenomic era - Ze-Tao Jin; Richard G.J. Hodel; Dai-Kun Ma; Hui Wang; Guang-Ning Liu; Chen Ren; Bin-Jie Ge; Qiang Fan; Shui-Hu Jin; Chao Xu; Jun Wu; Bin-Bin Liu (Molecular Phylogenetics and Evolution, 2023)

Edible electrospun zein nanofibrous scaffolds close the gaps in biofilm formation ability between microorganisms - Meng-Xin Hu; Fei He; Cheng-Kai Tu; Zhe-Xin Chen; Hui Teng; Xin Shao; Ge-Rui Ren; Ya-Xin Guo (Food Bioscience, 2023)

Inducing root redundant development to release oxygen: An efficient natural oxygenation approach for subsurface flow constructed wetland - Jingying Zhang; Qiuhui Yan; Ge Bai; Dun Guo; Yanbin Chi; Bin Li; Lei Yang; Yongxiang Ren (Environmental Research, 2023)

Impacts of coal use phase-out in China on the atmospheric environment: (1) emissions, surface concentrations and exceedance of air quality standards - Wendong Ge; Jie Li; Junfeng Liu; Chenyang Xu; Huihuang Wu; Yuhan Zhou; Yang Ren; Xian Wang; Leyi Zheng; Jingcheng Zhou; Xuesong Wang; Yue Qin (Atmospheric Environment, 2023)

Associations of 10 trace element levels in the whole blood with risk of three types of obesity in the elderly - Rui Zhan; Lin Liu; Maoyuan Yang; Yating Ren; Zhihao Ge; Jun Shi; Ke Zhou; Jiebao Zhang; Hongjuan Cao; Linsheng Yang; Kaiyong Liu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Retraction Note: Differentiation of Mesenchymal Stem Cells into Neural Stem Cells Using Cerebrospinal Fluid - Wei Ge; Chao Ren; Xin Duan; Deqin Geng; Caiyi Zhang; Xiaoyun Liu; Hao Chen; Meirong Wan; Runlu Geng (Cell Biochemistry and Biophysics, 2023)

Carbon chain length of perfluoroalkylated carboxylic acids determines inhibitory strength on gonadal 3β-hydroxysteroid dehydrogenases in humans, rats, and mice - Huina Zhang; Shaowei Wang; Ya Chen; Jingjing Li; Yingna Zhai; Yunbing Tang; Huitao Li; Jianmin Sang; Hong Wang; Jieqiang Lv; Ren-shan Ge (Toxicology Letters, 2023)

Experimental and numerical studies on the interaction between two identical slot jet H2/CO diffusion flames - Huanhuan Xu; Yi Ge; Shouyan Chen; Fanxing Meng; Zilin Zhu; Xiaohan Ren (Fuel, 2023)

Bisphenol analogues inhibit human and rat 17β-hydroxysteroid dehydrogenase 1: 3D-quantitative structure-activity relationship (3D-QSAR) and in silico docking analysis - Sailing Chen; Shaowei Wang; Jingyi Zheng; Han Lu; Huiqian Chen; Yunbing Tang; Nan Wang; Yang Zhu; Yiyan Wang; Ping Duan; Ren-shan Ge (Food and Chemical Toxicology, 2023)

Temporal-spatial Generation of Astrocytes in the Developing Diencephalon - Wentong Hong; Pifang Gong; Xinjie Pan; Zhonggan Ren; Yitong Liu; Guibo Qi; Jun-Liszt Li; Wenzhi Sun; Woo-Ping Ge; Chun-Li Zhang; Shumin Duan; Song Qin (Neuroscience Bulletin, 2023)
Astrocytes are the largest glial population in the mammalian brain. However, we have a minimal understanding of astrocyte development, especially fate specification in different regions of the brain. Through lineage tracing of the progenitors of the third ventricle (3V) wall via in-utero electroporation in the embryonic mouse brain, we show the fate specification and migration pattern of astrocytes derived from radial glia along the 3V wall. Unexpectedly, radial glia located in different regions along the 3V wall of the diencephalon produce distinct cell types: radial glia in the upper region produce astrocytes and those in the lower region produce neurons in the diencephalon. With genetic fate mapping analysis, we reveal that the first population of astrocytes appears along the zona incerta in the diencephalon. Astrogenesis occurs at an early time point in the dorsal region relative to that in the ventral region of the developing diencephalon. With transcriptomic analysis of the region-specific 3V wall and lateral ventricle (LV) wall, we identified cohorts of differentially-expressed genes in the dorsal 3V wall compared to the ventral 3V wall and LV wall that may regulate astrogenesis in the dorsal diencephalon. Together, these results demonstrate that the generation of astrocytes shows a spatiotemporal pattern in the developing mouse diencephalon.

Azole fungicides inhibit human and rat gonadal 3β-hydroxysteroid dehydrogenases: Structure-activity relationship and in silico docking analysis - Jianmin Sang; Hong Wang; Yang Yu; Zhongyao Ji; Miaomiao Xia; Ting Hao; Linxi Li; Ren-shan Ge (Food and Chemical Toxicology, 2023)

Dynamic simulation and analysis of land use competition patterns to support sustainable territorial spatial management: a case study of Shenyang City, Northeast China - Quanxi Wang; Ge Song; Gaofeng Ren; Hongjun Sui; Ruiqing Su (Environmental Science and Pollution Research, 2023)

Hyperspectral image classification Based on weakened Laplacian pyramid and guided filtering - Wuli Wang; Ge Wang; Yumeng Jiang; Wenhui Guo; Guangbo Ren; Jianbu Wang; Yanjiang Wang (International Journal of Remote Sensing, 2023)

A comprehensive investigation on source apportionment and multi-directional regional transport of volatile organic compounds and ozone in urban Zhengzhou - Xiaoxi Zeng; Mengjuan Han; Ge Ren; Gege Liu; Xiaoning Wang; Kailun Du; Xiaodong Zhang; Hong Lin (Chemosphere, 2023)

Halogenated bisphenol A derivatives potently inhibit human, rat, and mouse gonadal 3β-hydroxysteroid dehydrogenases: Structure-activity relationship and in silico molecular docking analysis - Yang Yu; Mengyun Wang; Ya Chen; Chengshuang Pan; Qianjin Fei; Yang Zhu; Huitao Li; Ren-shan Ge (Toxicology Letters, 2023)

Trichlorfon blocks androgen synthesis and metabolism in rat immature Leydig cells - Huan Chen; Yaoyao Dong; Huitao Li; Zhili Chen; Ming Su; Qiqi Zhu; Ren-Shan Ge; Xinjun Miao (Reproductive Toxicology, 2023)

Practical application for legacy acid mine drainage (AMD) prevention and treatment technologies in karst-dominated regions: A case study - Xin Li; Hujun Ren; Zhimin Xu; Ge Chen; Shangguo Zhang; Li Zhang; Yajun Sun (Journal of Contaminant Hydrology, 2023)

A novel approach to electromagnetic wave absorbing material design: Utilizing nano-antenna arrays for efficient electromagnetic wave capture - Shikun Hou; Ying Wang; Feng Gao; Hua Yang; Fei Jin; Li Ren; Qiong Wu; Hongliang Ge; Yahui Wang (Chemical Engineering Journal, 2023)

Fine-tuning channel structure and surface chemistry of stable bismuth-organic frameworks for efficient C2H4 purification through reversely trapping CO2 and C2H2 - Chunlian Hao; Zhencui Ge; Rajamani Krishna; Hao Ren; Houyu Zhu; Yuhua Chi; Wen Zhao; Xiuping Liu; Wenyue Guo (Chemical Engineering Journal, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Responses of soil carbon cycling microbial functional genes to nitrogen and phosphorus addition in saline-sodic soils - Xuejun Du; Yanning Ge; Yun Zhang; Hao Hu; Yiying Zhang; Ziye Yang; Xueqin Ren; Shuwen Hu; Haojie Feng; Yuling Song (Plant and Soil, 2023)

Assembly Processes and Biogeographical Characteristics of Soil Bacterial Sub-communities of Different Habitats in Urban Green Spaces - Yulian Ren; Qiuyu Shao; Wei Ge; Xin Li; Haiyan Wang; Chunbo Dong; Yanwei Zhang; Sunil Kumar Deshmukh; Yanfeng Han (Current Microbiology, 2023)

Protective efficacy of recombinant proteins AMA1 and IMP1 in rabbits infected with Eimeria intestinalis - Jie Xiao; Wei He; Changming Xiong; Ge Hao; Jiayan Pu; Hao Chen; Liwen Xu; Yuhua Zhu; Yongjun Ren; Guangyou Yang (Veterinary Parasitology, 2023)

Recent advances in the control of volatile organic compounds emissions from indoor wood-based panels: A comprehensive review - Yang Yang; Zhongfeng Zhang; Lei Zhang; Feifei Song; Yi Ren; Xu Zhang; Jijuan Zhang; Rock Keey Liew; Shin Ying Foong; William Woei Fong Chong; Su Shiung Lam; Meenakshi Verma; et al. (Science of The Total Environment, 2023)

Comparative analysis of the molecular response characteristics in Platycodon grandiflorus irradiated with heavy ion beams and X-rays - Xiao Liu; Yan Du; Chaoli Xu; Fusheng Wang; Xuehu Li; Luxiang Liu; Xiaohui Ma; Yuanmeng Wang; Linghui Ge; Weibin Ren; Ling Jin; Libin Zhou (Life Sciences in Space Research, 2023)

Root vertical spatial stress: A method for enhancing rhizosphere effect of plants in subsurface flow constructed wetland - Jingying Zhang; Zhiyong Shao; Bin Li; Ge Bai; Lei Yang; Yanbin Chi; Min Wang; Yongxiang Ren (Environmental Research, 2023)

The complete mitochondrial genome of Eulaelaps huzhuensis (Mesostigmata: Haemogamasidae) - Hui-Juan Yang; Zhi-Hua Yang; Tian-Guang Ren; Wen-Ge Dong (Experimental and Applied Acarology, 2023)
Some mites of the family Haemogamasidae can transmit a variety of zoonotic diseases and have important public health and safety implications. Currently, however, little attention has been paid to molecular data of Haemogamasidae species, limiting our understanding of their evolutionary and phylogenetic relationships. In this study, the complete mitochondrial genome of Eulaelaps huzhuensis was determined for the first time, and its genomic information was analyzed in detail. The mitochondrial genome of E. huzhuensis is 14,872 bp in length with 37 genes and two control regions. The base composition showed a distinct AT preference. Twelve protein-coding genes have a typical ATN as the start codon, and three protein-coding genes have incomplete stop codons. During the folding of tRNA genes, a total of 30 mismatches occurred, and three tRNA genes had an atypical cloverleaf secondary structure. The order of the E. huzhuensis mitochondrial genome arrangement is a new type of rearrangement in Mesostigmata. The phylogenetic analysis confirmed that the family Haemogamasidae is a monophyletic branch and does not belong to a subfamily of the Laelapidae. Our results lay the foundation for subsequent studies on the phylogeny and evolutionary history of the family Haemogamasidae.

Specialist species of fungi and bacteria are more important than the intermediate and generalist species in near-urban agricultural soils - Yulian Ren; Wei Ge; Chunbo Dong; Haiyan Wang; Shui Zhao; Chenglong Li; Jinhui Xu; Zongqi Liang; Yanfeng Han (Applied Soil Ecology, 2023)

Inhibited expression of amylases and cellulases in crabs with hepatopancreatic necrosis disease and their regulation by EcR and HR38 - Qian Ren; Yuqi Zhao; Xingkong Ma; Jiachun Ge; Xin Huang (Frontiers in Marine Science, 2023)
Hepatopancreatic necrosis disease (HPND) is a serious threat to the stable and sustainable development of the Chinese mitten crab farming industry. Studies have found that the hepatopancreas is the main lesion organ in HPND crabs, capable of causing metabolic abnormalities and non-feeding (starvation state). Here, four amylases (named as EsAmy1-4 ) and four cellulases (endo-beta-1, 4-glucanase, named as EsGlu1-4 ) that relate to carbohydrate metabolism were cloned from Eriocheir sinensis . Our studies found that the expressions of EsAmy1-4 and EsGlu1-4 were significantly decreased in the hepatopancreas of crabs with HPND. Moreover, the expressions of two important regulatory factors of carbohydrate metabolism, hormone receptor 38 ( EsHR38 ) and ecdysone receptor ( EsEcR ), were remarkably decreased in the hepatopancreas of crabs with HPND. Further studies found that knockdown of EsHR38 and EsEcR could down-regulated the expressions of EsAmy1-4 and EsGlu1-4 . In addition, downregulation of EsEcR could decrease the expression of EsHR38 . Hence, HPND causes down-regulation of EsEcR expression, inhibits the transcription of EsHR38 , further inhibits the expression of EsAmy1-4 and EsGlu1-4 , and then leads to the abnormal carbohydrate metabolism. The abnormalities of carbohydrate metabolism may result in the abnormal food intake in crabs. This study provides new evidence for further understanding the mechanism of HPND.

Leydig cell development in pubertal male rats is blocked by perfluorotetradecanoic acid through decreasing AMPK-mTOR-autophagy pathway - Yunbing Tang; Lei Shi; Shaowei Wang; Han Lu; Huitao Li; Jieqiang Lv; Ren-shan Ge; Yingfen Ying (Toxicology Letters, 2023)

Emission and gas-particle partitioning characteristics of atmospheric halogenated and organophosphorus flame retardants in decabromodiphenyl ethane-manufacturing functional areas - Helong Ren; Xiang Ge; Zenghua Qi; Qinhao Lin; Guofeng Shen; Yingxin Yu; Taicheng An (Environmental Pollution, 2023)

Cyano group modified graphitic carbon nitride supported Ru nanoparticles for enhanced CO2 methanation - Tianfen Huang; Ruiyi Wang; Jin Zhang; Jiapei Wang; Hui Ge; Jun Ren; Zhanfeng Zheng (Chemical Engineering Journal, 2023)

Duox mediated ROS production inhibited WSSV replication in Eriocheir sinensis under short-term nitrite stress - Rui Jia; Xiaoling Dai; Yanfang Li; Xintong Yang; Xiuwen Min; Derun Quan; Peng Liu; Xin Huang; Jiachun Ge; Qian Ren (Aquatic Toxicology, 2023)

The Occurrence and Characteristics of Microplastic Pollution in the Agricultural Soils of Anhui Province, in Eastern China - Xue Ren; Jianhua Ge; Zhou Wei; Wan Zhang; Hao Wen (Water, Air, & Soil Pollution, 2023)

Organophosphate esters in the seawater of the Bohai Sea: Environmental occurrence, sources and ecological risks - Rongguang Xing; Peng Zhang; Nan Zheng; Hao Ji; Ren Shi; Linke Ge; Hongrui Ma (Marine Pollution Bulletin, 2023)

Benzophenone-type ultraviolet filters inhibit human and rat placental 3β-hydroxysteroid dehydrogenases: Structure-activity relationship and in silico docking analysis - Hao Lin; Shaowei Wang; Yunbing Tang; Zhiyan Hu; Xiaofang Chen; Huitao Li; Yang Zhu; Yiyan Wang; Yi Liu; Ren-shan Ge (Toxicology Letters, 2023)

Poly-γ-glutamic acid-producing Bacillus velezensis fermentation can improve the feed properties of soybean meal - Han Hu; Caiyun Wu; Fanglan Ge; Yao Ren; Wei Li; Jiao Li (Food Bioscience, 2023)

How to drive strategic green innovation behavior? A qualitative comparative analysis (QCA) based on Chinese manufacturing enterprises - Jing Xiao; Ping Zeng; Ge Ren; Leimin Zhang (Environmental Science and Pollution Research, 2023)

Lysinibacillus capsici 38,328 isolated from agricultural soils as a promising probiotic candidate for intestinal health - Huinan Chen; Xiaoyi Sun; Huilin He; Hongkun Ren; Haoyuan Duan; Chuankun Zhang; Qingru Chang; Runxiang Zhang; Junwei Ge (Archives of Microbiology, 2023)

The Subsurface and Surface Indian Ocean Dipoles and Their Association with ENSO in CMIP6 models - Ge Song; Rongcai Ren (Advances in Atmospheric Sciences, 2023)

Transcriptome analysis reveals the feeding response and oxidative stress in juvenile Micropterus salmoides fed a low-fish-meal diet with enzyme-hydrolysed intestinal mucosa protein substitution - Heng Yu; Xianping Ge; Lin Zhang; Xiaoru Chen; Mingchun Ren; Hualiang Liang (Aquaculture, 2023)

Homogenization of trees in urban green spaces along the moisture gradient in China - Yan Ouyang; Yi Chen; Guofu Yang; Yuan Ren; Mingjian Yu; Jie Chang; Ying Ge (Urban Forestry & Urban Greening, 2023)

Dissolved biochar fractions and solid biochar particles inhibit soil acidification induced by nitrification through different mechanisms - Ren-Yong Shi; Ni Ni; Ru-Hai Wang; Jackson Nkoh Nkoh; Xiao-Ying Pan; Ge Dong; Ren-Kou Xu; Xiu-Min Cui; Jiu-Yu Li (Science of The Total Environment, 2023)

Application of microwave hydrothermal synthesis for the solidification of copper: Effect of heavy metal content and microwave time - Shuqiong Luo; Yali Ge; Minghui Zhao; Lei Yang; Jun Ren (Process Safety and Environmental Protection, 2023)

Halogen atoms determine the inhibitory potency of halogenated bisphenol A derivatives on human and rat placental 11β-hydroxysteroid dehydrogenase 2 - Lei Shi; Bingru Zhang; Yingfen Ying; Yunbing Tang; Shaowei Wang; Yang Zhu; Huitao Li; Ren-shan Ge; Yi Liu (Food and Chemical Toxicology, 2023)

The analysis of pesticides and fungicides in the inhibition of human and rat placental 3β-hydroxysteroid dehydrogenase activity: Mode of inhibition and mechanism - Yingna Zhai; Shaowei Wang; Bingru Zhang; Yunbing Tang; Hong Wang; Jingjing Li; Zhiyan Hu; Yiyan Wang; Huitao Li; Ren-shan Ge (Toxicology Letters, 2023)

Direct inhibition of human and rat 11β-hydroxysteroid dehydrogenase 2 by per- and polyfluoroalkyl substances: Structure-activity relationship and in silico docking analysis - Congcong Zhao; Shaowei Wang; Yingna Zhai; Mengyun Wang; Yunbing Tang; Huitao Li; Young Jun Im; Ren-shan Ge (Toxicology, 2023)

Mechanical properties of auxetic circular and square tubes filled with aluminum foam - Ru Yuan Huo; Dong Han; Yi Zhang; Wei Jiang; Le Yang Fan; Xin Wei Peng; Ge Chen Jie Shi; Ming Hao Chu; Xiang Yu Zhang; Yi Min Xie; Xin Ren (Engineering Structures, 2023)

Manganese dioxide eliminates the phytotoxicity of aerobic compost products and converts them into a plant friendly organic fertilizer - Fangyi Pei; Xinbo Cao; Yangcun Sun; Jie Kang; YanXin Ren; Jingping Ge (Bioresource Technology, 2023)

Isothermal exponential amplification reactions triggered by circular templates (cEXPAR) targeting miRNA - Xue-mei Qu; Xiao-dong Ren; Ning Su; Xian-ge Sun; Shao-li Deng; Wei-ping Lu; Qing Huang (Molecular Biology Reports, 2023)

Study on the dust migration law and a spray dust suppression scheme in transportation roadway - Deji Jing; Mingxing Ma; Shaocheng Ge; Tian Zhang; Xiangxi Meng; Shuaishuai Ren (Environmental Science and Pollution Research, 2023)

Jumping of flea beetles onto inclined platforms - Le Zong; Jianing Wu; Pingping Yang; Jing Ren; Guanya Shi; Siqin Ge; David L. Hu (Journal of Comparative Physiology A, 2023)

Immobilizing arsenic in soil via amine metal complex: a case study using iron-ethylenediamine - Qilin Lv; Tairan Zhou; Tianhao Wang; Shuhan Wang; Yanning Ge; Yuling Song; Xueqin Ren; Shuwen Hu (Environmental Science and Pollution Research, 2023)

A systematic review, meta-analysis and meta-regression of the global prevalence of foodborne Vibrio spp. infection in fishes: A persistent public health concern - Jun-Yang Ma; Xin-Kun Zhu; Ren-Ge Hu; Ze-Zheng Qi; Wen-Chao Sun; Zhi-Peng Hao; Wei Cong; Yuan-Huan Kang (Marine Pollution Bulletin, 2023)

Spatiotemporal variation of cultivated land ecosystem stability in typical regions of Lower Liaohe Plain China based on stress - buffer - response - Hongjun Sui; Ge Song; Wanying Liu; Yuxin Zhang; Ruiqing Su; Quanxi Wang; Gaofeng Ren; Yuqi Mi (Science of The Total Environment, 2023)

Identification and localization of morphological feature-specific metabolites in Reynoutria multiflora roots - Meng-Ting Cai; Yu Zhou; Wen-Luan Ding; Yu-Hong Huang; Ying-Shan Ren; Zhi-You Yang; Lei Zhang; Fei Sun; Hai-Biao Guo; Liang-Yun Zhou; Zhi-Hong Gong; Xiu-Hong Piao; et al. (Phytochemistry, 2023)

Effects of plant physiological responses under nitrogen stress on pollutant removal in subsurface constructed wetlands - Zihui Yao; Yongxiang Ren; Bin Li; Ge Bai; Siqi Zhao; Lei Yang; Yanbin Chi (Journal of Water Process Engineering, 2023)

Analysis of microbial community and its correlation with flavor compounds during Congee fermentation - Yang Yang; You Na Wu; Li Ge Er Ce; Xi Ge Bu Ren Ge; Quan Shuang; Feng Mei Zhang (Food Bioscience, 2023)

Axial nitrogen-coordination engineering over Fe-Nx active species for enhancing Fenton-like reaction performance - Fenli Liu; Yujing Ren; Jianglin Duan; Pengcheng Deng; Jianyu Lu; Huibin Ge; Xin Liu; Qixing Xia; Haifeng Qi; Na Yang; Yong Qin (Chemical Engineering Journal, 2023)

Applicability evaluation and error analysis of TMPA and IMERG in Inner Mongolia Autonomous Region, China - Zheng Ge; Ruihong Yu; Penghang Zhu; Yanling Hao; Yuan Li; Xinyu Liu; Zhuangzhuang Zhang; Xiaohui Ren (Theoretical and Applied Climatology, 2023)

Comprehensive profiles of per- and polyfluoroalkyl substances in Chinese and African municipal wastewater treatment plants: New implications for removal efficiency - Lulin Jiang; Jingzhi Yao; Ge Ren; Nan Sheng; Yong Guo; Jiayin Dai; Yitao Pan (Science of The Total Environment, 2023)

Inhibition of human and rat placental 3β-hydroxysteroid dehydrogenase/Δ5,4-isomerase activities by insecticides and fungicides: Mode action by docking analysis - Jingjing Li; Fuhong Tian; Yunbing Tang; Lei Shi; Shaowei Wang; Zhiyan Hu; Yang Zhu; Yiyan Wang; Huitao Li; Ren-shan Ge; Xiaoheng Li (Chemico-Biological Interactions, 2023)

Aberrant Topological Properties of Brain Functional Network in Children with Obstructive Sleep Apnea Derived from Resting-State fMRI - Tingting Ji; Xuemin Ren; Ting Long; Xiaodan Li; Lin Mei; Wentong Ge; Jie Zhang; Shengcai Wang; Yongli Guo; Zhifei Xu; Yun Peng; Jiangang Liu; et al. (Brain Topography, 2023)

An improved global grid model for calibrating zenith tropospheric delay for GNSS applications - Liangke Huang; Ge Zhu; Hua Peng; Lilong Liu; Chao Ren; Weiping Jiang (GPS Solutions, 2023)

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)

How can the positive Indian Ocean Dipole events co‐occur with La Niña? - Ge Song; Rongcai Ren (International Journal of Climatology, 2022)
Positive/negative Indian Ocean Dipole (IOD) tends to co‐occur with El Niño/La Niña. Five positive IODs, however, are observed under La Niña condition in 1961, 1966, 1967, 2007, and 2011. This study uses the monthly ocean temperature and atmospheric reanalysis datasets from ECMWF to investigate how these positive IOD events occurred. It is found that the five positive IODs are consistently accompanied by a moderately strong positive subsurface IOD (Sub‐IOD) event that initiated earlier. The Sub‐IOD‐related oceanic dynamical processes including oceanic Kelvin and Rossby waves help to promote the development of the positive IODs. More specifically, the equatorial easterly anomalies in the Tropical Indian Ocean (TIO) that are crucial for the development of the positive Sub‐IODs and IODs in 1961/2011 are triggered by an anticyclonic curl over South Indian Ocean that is induced by a Southern Hemispheric Indian Ocean Subtropical Dipole mode. The crucial equatorial easterly anomalies in 1967 are triggered by a thermocline warming in the southwestern TIO induced by westward downwelling oceanic Rossby waves, while in 1966/2007, the equatorial easterly anomalies are connected with the anomalous Walker circulation resulting from the certain sea surface temperature anomaly pattern over the equatorial Pacific. On the other hand, the remote effects of La Niña on TIO are relatively weaker, being overwhelmed by the above triggering processes.

Evaluation of the coagulation properties of magnesium hydroxide for removal combined contamination of reactive dyes and microfibers - Yingying Duan; Jianhai Zhao; Xiuming Qiu; Xiaoli Deng; Xiaoyu Ren; Wenqi Ge; Hongying Yuan (Environmental Science and Pollution Research, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Microfossil evidence of rice cultivation on the Southeast China Coast 7500 years ago - Xinxin Zuo; Jinqi Dai; Wei Wu; Jianhui Jin; Wei Ge; Yinping Wang; Lin Ren; Yingjun Lin; Yaoyao Pei; Hui Xie (Science China Earth Sciences, 2022)

Genotyping USDA rice (Oryza spp.) mini-core collection with functional markers for important agronomic traits - Kehu Li; Lily Yan Wang; Huanhuan Ren; Yongyi Ge (Genetic Resources and Crop Evolution, 2022)

The role of N6-methyladenosine methylation in environmental exposure-induced health damage - Yanlu Feng; Tong Liu; Siyi Xu; Yiyi Ren; Yiling Ge; Lihong Yin; Yuepu Pu; Geyu Liang (Environmental Science and Pollution Research, 2022)

Transport Patterns and Potential Sources of Atmospheric Pollution during the XXIV Olympic Winter Games Period - Yuting Zhang; Xiaole Pan; Yu Tian; Hang Liu; Xueshun Chen; Baozhu Ge; Zhe Wang; Xiao Tang; Shandong Lei; Weijie Yao; Yuanzhe Ren; Yongli Tian; et al. (Advances in Atmospheric Sciences, 2022)
The attainment of suitable ambient air quality standards is a matter of great concern for successfully hosting the XXIV Olympic Winter Games (OWG). Transport patterns and potential sources of pollutants in Zhangjiakou (ZJK) were investigated using pollutant monitoring datasets and a dispersion model. The PM 2.5 concentration during February in ZJK has increased slightly (28%) from 2018 to 2021, mostly owing to the shift of main potential source regions of west-central Inner Mongolia and Mongolian areas (2015–18) to the North China Plain and northern Shanxi Province (NCPS) after 2018. Using CO as an indicator, the relative contributions of the different regions to the receptor site (ZJK) were evaluated based on the source-receptor-relationship method (SRR) and an emission inventory. We found that the relative contribution of pollutants from NCPS increased from 33% to 68% during 2019–21. Central Inner Mongolia (CIM) also has an important impact on ZJK under unfavorable weather conditions. This study demonstrated that the effect of pollution control measures in the NCPS and CIM should be strengthened to ensure that the air quality meets the standard during the XXIV OWG.

Stable carbon isotopes of dissolved inorganic carbon in the Western North Pacific Ocean: Proxy for water mixing and dynamics - Tiantian Ge; Chunle Luo; Peng Ren; Hongmei Zhang; Di Fan; Hongtao Chen; Zhaohui Chen; Jing Zhang; Xuchen Wang (Frontiers in Marine Science, 2022)
The uptake of atmospheric CO 2 and the cycle of dissolved inorganic carbon (DIC) in the ocean are the major mechanisms and pathways controlling global climate change and carbon cycling. The stable carbon isotope (δ 13 C) of DIC, therefore, provides an important tracer for processes such as air-sea exchange, photosynthesis, and water dynamics in the ocean. Here, we present new δ 13 C-DIC data on water samples collected from a north-south transect (13°N–40°N, 150°E) in the western North Pacific (NP) Ocean in November 2019 and compare the results with those previously reported for similar transects (149.3°E) during WOCE and CLIVAR projects over the past three decades. The values of δ 13 C-DIC, ranging from -0.83‰ to 0.86‰, were higher in the surface waters and decreased with depth. The high δ 13 C-DIC values in the surface waters were influenced primarily by isotopic fractionation during air-sea exchange and photosynthesis. With depth, the movement of different water masses and mixing, as well as bathypelagic respiration in the dark water of the ocean, all play important roles in influencing the distribution and isotopic signatures of δ 13 C-DIC in the western NP Ocean. The δ 13 C-DIC values of the 0–200 m water layer varied from -0.17‰ to 0.86‰, with lower values at high latitudes, affected by the low δ 13 C-DIC values carried by the Oyashio Current to the Kuroshio Extension (KE) region. A downward trend was present in the δ 13 C-DIC signature from north to south in the North Pacific Intermediate Water (NPIW) and Pacific Deep Water (PDW) in the western NP, which reflected the remineralization of organic matter with a horizontal transport of NPIW and PDW. We found a strong 13 C Suess Effect in the upper 2,000 m in the western NP Ocean, and δ 13 C-DIC at the surface (<50 m) has decreased by 0.60‰-0.85‰ since 1993. The mean δ 13 C-DIC change in the surface ocean was estimated at 0.28‰ per decade between 1993 and 2019. The air-sea exchange and water mixing in the study area may have accelerated the absorption of anthropogenic CO 2 in recent years, which likely caused a slightly faster rate of decrease in the δ 13 C-DIC from 2005–2019 than that observed from 1993–2005.

Dietary Protein Modifies Hepatic Glycolipid Metabolism, Intestinal Immune Response, and Resistance to Streptococcus agalactiae of Genetically Improved Farmed Tilapia (GIFT: Oreochromis niloticus) Exposed to High Temperature - Dongyu Huang; Hualiang Liang; Jian Zhu; Mingchun Ren; Xianping Ge (Fishes, 2022)
The present study investigates the effects of dietary protein levels on glucolipid metabolism, immune function, and resistance to Streptococcus agalactiae of genetically improved farmed tilapia (GIFT) exposed to high temperature. Six practical diets were prepared to feed 360 fish (initial weight 43.78 ± 0.12 g) with graded protein levels (26.45%, 29.28%, 31.69%, 33.68%, 36.18%, and 38.75% dry matter). The results showed that 26.45% dietary protein significantly improved glycolysis by increasing PK mRNA levels, while the 29.28% and 31.69% dietary protein levels promoted gluconeogenesis by increasing PEPCK and G6Pase mRNA levels. For lipid metabolism, 26.45% dietary protein enhanced lipid synthesis by increasing PPAR-γ, SREBP1c, and FAS mRNA levels, while 31.69% dietary protein enhanced the level of lipolysis by increasing the PPAR-α and CPT1 mRNA levels. The highest plasma TG and TC contents were observed in the 29.28% and 31.69% dietary protein groups, respectively. In terms of antioxidants and immunity, the 31.69% dietary protein level activated the expression levels of HSP90 mRNA, thus increasing the expression levels of antioxidant-related genes (CAT, SOD, and GPx), and upregulating the anti-inflammatory factor IL-10 mRNA levels. In addition, regarding the antioxidant enzymes, the highest GSH content was found in the 29.28% dietary protein group, while the 31.69% dietary protein group had the maximum GSH-Px activity. The lowest plasma ALT and AST activities were observed in the 31.69% dietary protein group. Ultimately, the survival rate of juvenile GIFT fed 31.69% dietary protein was highest after a Streptococcus agalactiae challenge. Overall, 29.28–31.69% dietary protein was recommended in the diet of GIFT in a high-temperature environment.

Optical Characteristics of Chromophoric Dissolved Organic Matter (CDOM) in Upstream and Downstream Lakes of Taihu Lake Basin: New Insights for Water Environmental Management - Weixiang Ren; Xiaodong Wu; Bingfa Chen; Jianying Chao; Xuguang Ge; Jiuyun Yang; Hui Yang (Chinese Geographical Science, 2022)

Versatile superhydrophobic bismuth molybdate cotton fabric for oil/water separation and decompose dyestuff - Jie Yue; Shaowang Tang; Bo Ge; Min Wang; Guina Ren; Xin Shao (Environmental Science and Pollution Research, 2022)

Dissolved Organic Carbon Along a Meridional Transect in the Western North Pacific Ocean: Distribution, Variation and Controlling Processes - Tiantian Ge; Chunle Luo; Peng Ren; Hongmei Zhang; Hongtao Chen; Zhaohui Chen; Jing Zhang; Xuchen Wang (Frontiers in Marine Science, 2022)
Dissolved organic carbon (DOC) in the ocean is one of the largest reduced and exchangeable organic carbon pools on Earth and plays important roles in carbon cycling and biogeochemical processes in the ocean. Here, we report the concentrations and distributions of DOC in water samples collected along a meridional transect in the western North Pacific (NP) Ocean in November 2019. Concentrations of DOC ranged from 33-102 μM, were higher in surface water, decreased rapidly with depth to 1,000 m, and then remained relatively constant. The labile fraction of DOC accounted for 20-40% of the surface bulk DOC and was respired very rapidly in the upper 200 m depth. The semi-labile fraction of DOC accounted for 15-20% of the surface bulk DOC and was exported downward and turned over at water depths of 200-2,000 m. The formation of NP Intermediate Water (NPIW) in the Kuroshio Extension (KE) region is a major process carrying some surface semi-labile DOC down. The Low concentrations of DOC (33-44 μM) were present in the entire water column below 1,000 m along the transect in the NP. Primary production and microbial consumption played major roles in the concentration and distribution of DOC in the euphotic zone, and hydrodynamic mixing and circulation of different water masses appear to be dominant factors controlling the distribution and dynamics of DOC in the deep water of the western NP.

Regulation of OsLPR1 gene on the formation of rice root iron plaque under low phosphorus - Yan Ding; Menglian Ren; Shuangrong Mo; Jing Liu; Zegang Wang; Cailin Ge; Yulong Wang (Plant Biotechnology Reports, 2022)

Recent advances in the structure, synthesis, and applications of natural polymeric hydrogels - Khalid Gul; Ren-You Gan; Cui-Xia Sun; Ge Jiao; Ding-Tao Wu; Hua-Bin Li; Ahmad Kenaan; Harold Corke; Ya-Peng Fang (Critical Reviews in Food Science and Nutrition, 2022)

Characterization and mutagenesis of a novel Mycobacterium smegmatis-derived glutamate decarboxylase active at neutral pH - Yudi Li; Guiying Chen; Fanglan Ge; Ting Dang; Yao Ren; Bei Zeng; Wei Li (World Journal of Microbiology and Biotechnology, 2022)

Genetic variation and association mapping of phenolic, flavonoid content and antioxidant capacity in USDA rice mini-core collection - Kehu Li; Qingzhu Li; Lily Yan Wang; Huanhuan Ren; Yongyi Ge (Genetic Resources and Crop Evolution, 2022)

Impact paths of land urbanization on haze pollution: spatial nesting structure perspective - Feng Wang; Ge Wang; Juan Liu; Jing Ren; Mingru Dong (Natural Hazards, 2021)

The transcription factor PjERF1 enhances the biosynthesis of triterpenoid saponins in Panax japonicus - Qin Chen; Yilin Yu; Xiang Zhang; Ren Zhao; Jinyu Zhang; Diqiu Liu; Xiuming Cui; Feng Ge (Plant Biotechnology Reports, 2021)

Enhancement of Cd(II) adsorption by rice straw biochar through oxidant and acid modifications - Xian He; Zhi-neng Hong; Jun Jiang; Ge Dong; Hui Liu; Ren-kou Xu (Environmental Science and Pollution Research, 2021)

Characteristics of dissolved organic matter in lakes with different eutrophic levels in southeastern Hubei Province, China - Weixiang Ren; Xiaodong Wu; Xuguang Ge; Guiying Lin; Mengdie Zhou; Zijie Long; Xinhui Yu; Wei Tian (Journal of Oceanology and Limnology, 2021)

Study on elevation effect of blast wave propagation in high side wall of deep underground powerhouse - Congrui Zhang; Yongxiang Ge; Junlin Lv; Gaofeng Ren (Bulletin of Engineering Geology and the Environment, 2021)

Genomic and phylodynamic analysis of sapoviruses isolated in Henan Province, China - Jinjin Liu; Na Ren; Shanlei Hu; Lijun Zheng; Lili Ge; Shuhuan Ma; Yuqi Huo (Archives of Virology, 2021)

Factors associated with a SARS-CoV-2 recurrence after hospital discharge among patients with COVID-19: systematic review and meta-analysis - Meng-qi Yao; Qiu-xian Zheng; Jia Xu; Jing-wen Deng; Tian-tian Ge; Hai-bo Zhou; Feng-tian Wu; Xin-yu Gu; Qin Yang; Yan-li Ren; Gang Wang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Effects of Al stress on the growth and nitrogen uptake of maize varieties with different Al tolerance as related with Al chemical forms on root surfaces - Xiao-ying Pan; Ge Dong; Xian He; Ru-hai Wang; Ren-kou Xu; Ting-ting Mu (Journal of Soils and Sediments, 2020)

Nanochemoprevention with therapeutic benefits: An updated review focused on epigallocatechin gallate delivery - Qiong-Qiong Yang; Xin-Lin Wei; Ya-Peng Fang; Ren-You Gan; Min Wang; Ying-Ying Ge; Dan Zhang; Li-Zeng Cheng; Harold Corke (Critical Reviews in Food Science and Nutrition, 2020)

Effect of the total replacement of fishmeal with plant proteins and supplemental essential amino acids in the extruded diet on antioxidants genes, enzyme activities, and immune response in juvenile blunt snout bream - Ahmed Mokrani; Mingchun Ren; Hualiang Liang; Qiang Yang; Ke Ji; Hopeson Chisomo Kasiya; Xianping Ge (Aquaculture International, 2020)

An extra insertion of tandem repeat sequence in African swine fever virus, China, 2019 - Shengqiang Ge; Yutian Liu; Lin Li; Qinghua Wang; Jinming Li; Weijie Ren; Chunju Liu; Jingyue Bao; Xiaodong Wu; Zhiliang Wang (Virus Genes, 2019)

Lysine acetylation contributes to development, aflatoxin biosynthesis and pathogenicity in Aspergillus flavus - Guang Yang; Yuewei Yue; Silin Ren; Mingkun Yang; Yi Zhang; Xiaohong Cao; Yinchun Wang; Jia Zhang; Feng Ge; Shihua Wang (Environmental Microbiology, 2019)
Summary Aspergillus flavus is a pathogenic fungus that produces carcinogenic aflatoxins, posing a great threat to crops, animals and humans. Lysine acetylation is one of the most important reversible post‐translational modifications and plays a vital regulatory role in various cellular processes. However, current information on the extent and function of lysine acetylation and aflatoxin biosynthesis in A. flavus is limited. Here, a global acetylome analysis of A. flavus was performed by peptide pre‐fractionation, pan‐acetylation antibody enrichment and liquid chromatography–mass spectrometry. A total of 1313 high‐confidence acetylation sites in 727 acetylated proteins were identified in A. flavus . These acetylation proteins are widely involved in glycolysis/gluconeogenesis, pentose phosphate pathway, citric acid cycle and aflatoxin biosynthesis. AflO ( O ‐methyltransferase), a key enzyme in aflatoxin biosynthesis, was found to be acetylated at K241 and K384. Deletion of aflO not only impaired conidial and sclerotial developments, but also dramatically suppressed aflatoxin production and pathogenicity of A. flavus . Further site‐specific mutations showed that lysine acetylation of AflO could also result in defects in development, aflatoxin production and pathogenicity, suggesting that acetylation plays a vital role in the regulation of the enzymatic activity of AflO in A. flavus . Our findings provide evidence for the involvement of lysine acetylation in various biological processes in A. flavus and facilitating in the elucidation of metabolic networks.

Dietary leucine affects glucose metabolism and lipogenesis involved in TOR/PI3K/Akt signaling pathway for juvenile blunt snout bream Megalobrama amblycephala - Hualiang Liang; Ahmed Mokrani; Hopeson Chisomo-Kasiya; Ke Ji; Xianping Ge; Mingchun Ren; Bo Liu; Bingwen Xi; Ajun Sun (Fish Physiology and Biochemistry, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Omics for understanding the mechanisms of Streptomyces lydicus A01 promoting the growth of tomato seedlings - Qiong Wu; Mi Ni; Wei-Cheng Liu; Jian-Hong Ren; Ying-Hong Rao; Jie Chen; Cai-Ge Lu (Plant and Soil, 2018)

Dietary Chromium Picolinate Supplementation Affects Growth, Whole-Body Composition, and Gene Expression Related to Glucose Metabolism and Lipogenesis in Juvenile Blunt Snout Bream, Megalobrama amblycephala - Mingchun Ren; Ahmed Mokrani; Hualiang Liang; Ke Ji; Jun Xie; Xianping Ge; Bo Liu (Biological Trace Element Research, 2018)

Formation of the Permian Taipinggou igneous rocks, north of Luobei (Northeast China): implications for the subduction of the Mudanjiang Ocean beneath the Bureya–Jiamusi Massif - Yu Dong; Zhong-hua He; Zi-hui Ren; Wen-chun Ge; Hao Yang; Zheng Ji; Yue He (International Geology Review, 2018)

Electron acceptors for anaerobic oxidation of methane drive microbial community structure and diversity in mud volcanoes - Ge Ren; Anzhou Ma; Yanfen Zhang; Ye Deng; Guodong Zheng; Xuliang Zhuang; Guoqiang Zhuang; Danielle Fortin (Environmental Microbiology, 2018)
Summary Mud volcanoes (MVs) emit globally significant quantities of methane into the atmosphere, however, methane cycling in such environments is not yet fully understood, as the roles of microbes and their associated biogeochemical processes have been largely overlooked. Here, we used data from high‐throughput sequencing of microbial 16S rRNA gene amplicons from six MVs in the Junggar Basin in northwest China to quantify patterns of diversity and characterize the community structure of archaea and bacteria. We found anaerobic methanotrophs and diverse sulfate‐ and iron‐reducing microbes in all of the samples, and the diversity of both archaeal and bacterial communities was strongly linked to the concentrations of sulfate, iron and nitrate, which could act as electron acceptors in anaerobic oxidation of methane (AOM). The impacts of sulfate/iron/nitrate on AOM in the MVs were verified by microcosm experiments. Further, two representative MVs were selected to explore the microbial interactions based on phylogenetic molecular ecological networks. The sites showed distinct network structures, key species and microbial interactions, with more complex and numerous linkages between methane‐cycling microbes and their partners being observed in the iron/sulfate‐rich MV. These findings suggest that electron acceptors are important factors driving the structure of microbial communities in these methane‐rich environments.

Effects of autophagy on acid-sensing ion channel 1a-mediated apoptosis in rat articular chondrocytes - Ya-Ya Xie; Yue Li; Ren-peng Zhou; Bei-Bei Dai; Yue-jiao Qian; Xiao-shan Wu; Jin-fang Ge; Wei Hu; Fei-hu Chen (Molecular and Cellular Biochemistry, 2018)

Molecular characterization and identification of facilitative glucose transporter 2 (GLUT2) and its expression and of the related glycometabolism enzymes in response to different starch levels in blunt snout bream (Megalobrama amblycephala) - Hualiang Liang; Ahmed Mokrani; Hopeson Chisomo-Kasiya; Ogwok-Manas Wilson-Arop; Haifeng Mi; Ke Ji; Xianping Ge; Mingchun Ren (Fish Physiology and Biochemistry, 2018)

Effect of nitrite exposure on oxygen-carrying capacity and gene expression of NF-κB/HIF-1α pathway in gill of bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Wu-Xiao Zhang; Wen-Jing Pan; Hua-Liang Liang; Xian-Ping Ge; Yan-Shun Xu; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou; Si-Lei Xia (Aquaculture International, 2018)

Bioinformatic prediction and analysis of glucolipid metabolic regulation by miR-34a in Megalobrama amblycephala - Ling-Hong Miao; Wen-Jing Pan; Yan Lin; Xian-Ping Ge; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou (Genes & Genomics, 2017)

Adiponectin Suppresses T Helper 17 Cell Differentiation and Limits Autoimmune CNS Inflammation via the SIRT1/PPARγ/RORγt Pathway - Kai Zhang; Yawei Guo; Zhenzhen Ge; Zhihui Zhang; Yurong Da; Wen Li; Zimu Zhang; Zhenyi Xue; Yan Li; Yinghui Ren; Long Jia; Koon-Ho Chan; et al. (Molecular Neurobiology, 2017)

Up-regulation of Vps4A promotes neuronal apoptosis after intracerebral hemorrhage in adult rats - Jianbing Ren; Debin Yuan; Lili Xie; Xuelei Tao; Chenwei Duan; Yifeng Bao; Yunfeng He; Jianbin Ge; Hongjian Lu (Metabolic Brain Disease, 2017)

Antioxidant response of ridgetail white prawn Exopalaemon carinicauda to harmful dinoflagellate Prorocentrum minimum exposure and its histological change - Cuimin Mu; Xianyun Ren; Qianqian Ge; Jiajia Wang; Jian Li (Journal of Ocean University of China, 2017)

Plant species diversity reduces N2O but not CH4 emissions from constructed wetlands under high nitrogen levels - Wenjuan Han; Mengmeng Shi; Jie Chang; Yuan Ren; Ronghua Xu; Chongbang Zhang; Ying Ge (Environmental Science and Pollution Research, 2017)

A strategy for introducing an endangered plant Mosla hangchowensis to urban area based on nitrogen preference - Mei-Ying Fan; Kai-Xuan Pan; Wen-Juan Han; Yi-Jun Lu; Qi Shen; Meng Wang; Yuan Ren; Ze-Long Qu; Jie Chang; Ying Ge (Acta Physiologiae Plantarum, 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Growth performance and immune responses of gibel carp, Carassius auratus gibelio, fed with graded level of rare earth-chitosan chelate - Qun-lan Zhou; Jun Xie; Xian-ping Ge; H. Michael Habte-Tsion; Bo Liu; Mingchun Ren (Aquaculture International, 2016)

Magnetostratigraphic evidence for deep-sea erosion on the Pacific Plate, south of Mariana Trench, since the middle Pleistocene: potential constraints for Antarctic bottom water circulation - Xiguang Deng; Liang Yi; Greig A. Paterson; Huafeng Qin; Haifeng Wang; Huiqiang Yao; Jiangbo Ren; Junyi Ge; Hongzhou Xu; Chenglong Deng; Rixiang Zhu (International Geology Review, 2016)

Up-regulation of PSMB4 is associated with neuronal apoptosis after neuroinflammation induced by lipopolysaccharide - Jiansheng Shi; Xiaorong Liu; Changde Xu; Jianbin Ge; Jianbing Ren; Jun Wang; Xinjian Song; Shirong Dai; Weidong Tao; Hongjian Lu (Journal of Molecular Histology, 2015)

TCTP Expression After Rat Spinal Cord Injury: Implications for Astrocyte Proliferation and Migration - Jianbing Ren; Xingxing Mao; Minghao Chen; Weidong Zhang; Yang Liu; Chengwei Duan; Haiyan Zhang; Chi Sun; Weijie Wu; Xinjian Zhu; Jianbing Ge; Weidong Tao; et al. (Journal of Molecular Neuroscience, 2015)

Putative phage-display epitopes of the porcine epidemic diarrhea virus S1 protein and their anti-viral activity - Liyan Cao; Xuying Ge; Yu Gao; Dante S. Zarlenga; Kexiong Wang; Xunliang Li; Zhaoheng Qin; Xiangping Yin; Jisheng Liu; Xiaofeng Ren; Guangxin Li (Virus Genes, 2015)

Cloning of catalase and expression patterns of catalase and selenium-dependent glutathione peroxidase from Exopalaemon carinicauda in response to low salinity stress - Hai Ren; Jian Li; Jitao Li; Yu Ying; Hongxing Ge; Dongli Li; Tianji Yu (Acta Oceanologica Sinica, 2015)

Molecular cloning and expression analysis of Relish gene from the ridgetail white prawn Exopalaemon carinicauda - Qianqian Ge; Junping Liang; Jitao Li; Jian Li; Yafei Duan; Fazhen Zhao; Hai Ren (Fisheries Science, 2015)

Accuracy and reliability of multi-GNSS real-time precise positioning: GPS, GLONASS, BeiDou, and Galileo - Xingxing Li; Maorong Ge; Xiaolei Dai; Xiaodong Ren; Mathias Fritsche; Jens Wickert; Harald Schuh (Journal of Geodesy, 2015)

Mesenchymal stem cells inhibit Th17 cells differentiation via IFN-γ-mediated SOCS3 activation - Xingxia Liu; Shaoda Ren; Xuebin Qu; Chaozhuo Ge; Kai Cheng; Robert Chun Hua Zhao (Immunologic Research, 2015)

Reconstruction of statistical–dynamical model of the Western Pacific subtropical high and East Asian summer monsoon factors and its forecast experiments - Mei Hong; Ren Zhang; Cheng Zu Bai; Xi Chen; Dong Wang; Jingjing Ge (Natural Hazards, 2015)

RETRACTED ARTICLE: Differentiation of Mesenchymal Stem Cells into Neural Stem Cells Using Cerebrospinal Fluid - Wei Ge; Chao Ren; Xin Duan; Deqin Geng; Caiyi Zhang; Xiaoyun Liu; Hao Chen; Meirong Wan; Runlu Geng (Cell Biochemistry and Biophysics, 2015)

Remarkable reductions of PAKs in the brain tissues of scrapie-infected rodent possibly linked closely with neuron loss - Ge Meng; Chan Tian; Hui Wang; Yin Xu; Bao-Yun Zhang; Qi Shi; Chen Gao; Cao Chen; Xue-Yu Fan; Jing Wang; Kang Xiao; Ke Ren; et al. (Medical Microbiology and Immunology, 2014)

A strategy for fusion expression and preparation of functional glucagon-like peptide-1 (GLP-1) analogue by introducing an enterokinase cleavage site - Yang Liu; Limei Ren; Lingmiao Ge; Qingxin Cui; Xiaofang Cao; Yuanyuan Hou; Fang Bai; Gang Bai (Biotechnology Letters, 2014)

Salicylic Acid Enhances Resistance to Fusarium oxysporum f. sp. phaseoli in Common Beans (Phaseolus vulgaris L.) - Ren Feng Xue; Jing Wu; Lan Fen Wang; Matthew W. Blair; Xiao Ming Wang; Wei De Ge; Zhen Dong Zhu; Shu Min Wang (Journal of Plant Growth Regulation, 2014)

An Observational Study of Autologous Bone Marrow-Derived Stem Cells Transplantation in Seven Patients with Nervous System Diseases: A 2-Year Follow-Up - Chao Ren; Run-lu Geng; Wei Ge; Xiao-Yun Liu; Hao Chen; Mei-Rong Wan; De-Qin Geng (Cell Biochemistry and Biophysics, 2014)

Organic carbon mineralization responses to temperature increases in subtropical paddy soils - Ping Zhou; Yong Li; Xiu’e Ren; He’ai Xiao; Chengli Tong; Tida Ge; Philip C. Brookes; Jianlin Shen; Jinshui Wu (Journal of Soils and Sediments, 2014)

Assessment of private economic benefits and positive environmental externalities of tea plantation in China - Hui Xue; Xiaoyi Ren; Shiyu Li; Xu Wu; Hao Cheng; Bin Xu; Baojing Gu; Guofu Yang; Changhui Peng; Ying Ge; Jie Chang (Environmental Monitoring and Assessment, 2013)

Effects of perfluorooctanesulfonate and perfluorobutanesulfonate on the growth and sexual development of Xenopus laevis - Qin-Qin Lou; Yin-Feng Zhang; Zhen Zhou; Ya-Li Shi; Ya-Nan Ge; Dong-Kai Ren; Hai-Ming Xu; Ya-Xian Zhao; Wu-Ji Wei; Zhan-Fen Qin (Ecotoxicology, 2013)

Accumulation flux of nitrogen in mudflats and its implications for benthic shellfish culture - Changzi Ge; Fan Zhang; Binduo Xu; Yiping Ren; Zhenlin Liang (Aquaculture International, 2013)

Is a new invasive herb emerging? Molecular confirmation and preliminary evaluation of natural hybridization between the invasive Sphagneticola trilobata (Asteraceae) and its native congener S. calendulacea in South China - Wei Wu; Ren-Chao Zhou; Guang-Yan Ni; Hao Shen; Xue-Jun Ge (Biological Invasions, 2013)

Thaxtomin A-deficient endophytic Streptomyces sp. enhances plant disease resistance to pathogenic Streptomyces scabies - Lan Lin; Hui Ming Ge; Tong Yan; Yan Hua Qin; Ren Xiang Tan (Planta, 2012)

Elevated O3 reduces the fitness of Bemisia tabaci via enhancement of the SA-dependent defense of the tomato plant - Hongying Cui; Yucheng Sun; Jianwei Su; Qin Ren; Chuanyou Li; Feng Ge (Arthropod-Plant Interactions, 2012)

Relationship of summer soil moisture with early winter monsoon and air temperature over eastern China - Ge Liu; Jun‐Ming Chen; Li‐Ren Ji; Shu‐Qing Sun (International Journal of Climatology, 2012)
The time‐lagged effect of summer soil moisture (SM) on ensuing winter climate in eastern China is examined. The East Asian winter monsoon (EAWM) in early winter (November) and associated air temperature over eastern China are shown to significantly correlate with the previous summer (June–August) SM in eastern China with a center located at the lower reaches of the Yellow River (LRYR). The positive anomalies of summer SM, persisting for a few months, may act as a buffer to defer the ground cooling of eastern China in early winter mainly through modulating thermal capacity. And the warmer ground of eastern China could lead to a warmer air temperature above the ground through direct land–air interactions and through indirectly adjusting the EAWM which is sensitive to the land–sea thermal contrast. These results provide an empirical predictor for the EAWM and for the variability of air temperature over eastern China in early winter. Copyright © 2011 Royal Meteorological Society

Century-Scale Responses of Ecosystem Carbon Storage and Flux to Multiple Environmental Changes in the Southern United States - Hanqin Tian; Guangsheng Chen; Chi Zhang; Mingliang Liu; Ge Sun; Arthur Chappelka; Wei Ren; Xiaofeng Xu; Chaoqun Lu; Shufen Pan; Hua Chen; Dafeng Hui; et al. (Ecosystems, 2012)

Anti-tumor Effects of All-trans Retinoic Acid are Enhanced by Genistein - Ren-Jie Zhou; Xue-Qin Yang; Dong Wang; Qian Zhou; Lei Xia; Meng-Xia Li; Lin-Li Zeng; Ge Wang; Zhen-Zhou Yang (Cell Biochemistry and Biophysics, 2012)

Antiviral activity and possible mechanisms of action of pentagalloylglucose (PGG) against influenza A virus - Ge Liu; Sheng Xiong; Yang-Fei Xiang; Chao-Wan Guo; Feng Ge; Chong-Ren Yang; Ying-Jun Zhang; Yi-Fei Wang; Kaio Kitazato (Archives of Virology, 2011)

Changes in ffh, uvrA, groES and dnaK mRNA Abundance as a Function of Acid-Adaptation and Growth Phase in Bifidobacterium longum BBMN68 Isolated from Healthy Centenarians - Junhua Jin; Songling Liu; Liang Zhao; Keshan Ge; Xueying Mao; Fazheng Ren (Current Microbiology, 2011)

Laboratory study of fluid viscosity induced ultrasonic velocity dispersion in reservoir sandstones - Tao He; Chang-Chun Zou; Fa-Gen Pei; Ke-Ying Ren; Fan-Da Kong; Ge Shi (Applied Geophysics, 2010)

Fluid sensitivity study of elastic parameters in low-medium porosity and permeability reservoir rocks - Fa-Gen Pei; Chang-Chun Zou; Tao He; Ge Shi; Gen-Gen Qiu; Ke-Ying Ren (Applied Geophysics, 2010)

Effects of long-term ouabain treatment on blood pressure, sodium excretion, and renal dopamine D1 receptor levels in rats - Yurong Zhang; Zuyi Yuan; Heng Ge; Yanping Ren (Journal of Comparative Physiology B, 2010)

Spatial and temporal variations and controlling factors of potential evapotranspiration in China: 1956–2000 - Ge Gao; Deliang Chen; Guoyu Ren; Yu Chen; Yaoming Liao (Journal of Geographical Sciences, 2006)

Pilot-Scale Fermentation and Purification of the Recombinant Allophycocyanin Over-Expressed in Escherichia coli - Baosheng Ge; Zhihong Tang; Liping Lin; Yuhong Ren; Yu Yang; Song Qin (Biotechnology Letters, 2005)

Computerized Tomography Examination of Damage Tests on Rocks Under Triaxial Compression - J. Ren; X. Ge (Rock Mechanics and Rock Engineering, 2004)